Organic film formation material, substrate for semiconductor device manufacturing, method for forming organic film, pattern formation method, and compound
Patent Information
- Application Number
- CN202410427614.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-10
- Filing Date
- 2024-04-10
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-04-10
AI Technical Summary
这种材料通过由作为交联剂的羟甲基化合物实现的交联、由空气中的氧的作用实现的芳香环的α位的氧化及其后由基于缩合的交联反应实现的固化作用而以对于下一工序中使用的涂布膜材料具有耐溶剂性的膜的形式成膜,但表现出该耐溶剂性的驱动力为氧化,因此,在非活性气体中无法满足充分的耐热性、平坦性等各性能
[0082]综上所述,本发明的化合物是对于形成即便在防止基板腐蚀的非活性气体中的成膜时也会固化而不产生副产物,兼具高耐热性、对于基板的良好密合性、高度的填埋和平坦化特性的有机膜而言有用的化合物。另外,包含该化合物(有机膜形成用化合物)的有机膜形成用材料成为形成具有优异的填埋/平坦化特性且兼具耐热性、耐蚀刻性等各特性的有机膜的材料。因此,如果是通过本发明的有机膜形成用材料而得到的有机膜,则兼具高度的填埋/平坦化特性,因而,形成不存在由填埋不良导致的微小空孔、由平坦性不足导致的有机膜表面凹凸的有机膜。因此,本发明的有机膜形成用材料作为例如二层抗蚀剂法、使用含硅中间膜的三层抗蚀剂法、使用含硅中间膜和有机防反射膜的四层抗蚀剂法之类的多层抗蚀剂法中的有机膜形成用材料或者半导体装置制造用平坦化材料极其有用。另外,由本发明的有机膜形成用材料形成的有机膜的耐热性优异,因此,即便在该有机膜上形成有CVD硬掩模的情况下,也不会因热分解而发生膜厚变动,适合于图案形成。进而,利用本发明的有机膜进行了平坦化的半导体装置基板在图案化时的工艺裕度变大,能够以良好的成品率制造半导体装置。并且,在半导体装置的制造工序中,如果利用本发明的图案形成方法来形成电路图案,则能够以良好的成品率制造半导体装置。
Smart Images

Figure CN118772680B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to materials for forming organic films, substrates for manufacturing semiconductor devices obtained using the materials, methods for forming organic films, patterning methods based on multilayer resist methods, and compounds applicable to the materials. Background Technology
[0002] Previously, photolithography, a common technique using light exposure, achieved high integration and high speed by miniaturizing patterns through the shortening of the light source wavelength, enabling semiconductor devices to achieve high integration and high speed. To form such fine circuit patterns on a substrate (the substrate being processed) for semiconductor device manufacturing, a method typically uses a patterned photoresist film as an etching mask and processes the substrate using dry etching. However, in reality, there is no dry etching method that can achieve complete etch selectivity between the photoresist film and the substrate. Therefore, substrate processing based on multilayer resist methods has become commonplace in recent years. This method involves sandwiching an intermediate film with an etch selectivity different from that of the photoresist film (hereinafter also referred to as the upper resist film) between the upper resist film and the substrate. After the upper resist film is patterned, the pattern of the upper resist film is used as a dry etching mask to transfer the pattern to the intermediate film through dry etching. Then, the intermediate film is used as a dry etching mask to transfer the pattern to the substrate through dry etching.
[0003] One type of multilayer photoresist method is the three-layer photoresist method, which can use general photoresist compositions used in single-layer photoresist methods. In this method, an organic lower layer film (hereinafter referred to as an organic film forming material) formed from a composition containing an organic resin is coated onto a substrate and calcined to form an organic lower layer film (hereinafter referred to as an organic film). Then, a photoresist intermediate film material (hereinafter referred to as a silicon-containing photoresist intermediate film material) formed from a composition containing a silicone resin is coated onto this substrate and calcined to form a silicon-containing film (hereinafter referred to as a silicon-containing photoresist intermediate film). A general organic photoresist film (photoresist upper layer film) is formed on this silicon-containing photoresist upper layer film. After patterning this photoresist upper layer film, when dry etching is performed using fluorine-based gas plasma, the organic photoresist upper layer film achieves a better etch selectivity than the silicon-containing photoresist intermediate film. Therefore, the pattern of the photoresist upper layer film can be transferred to the silicon-containing photoresist intermediate film. According to this method, even if a resist top film that does not have sufficient film thickness for processing the substrate and a resist top film that does not have sufficient dry etching resistance for processing the substrate are directly used, the silicon-containing resist intermediate film is usually of equal or less thickness compared to the resist top film. Therefore, patterns can be easily transferred onto the silicon-containing resist intermediate film. Next, if the patterned silicon-containing resist intermediate film is used as a dry etching mask, and the organic film is patterned by dry etching based on oxygen- or hydrogen-based gas plasma, patterns can be transferred onto an organic film that has sufficient dry etching resistance for processing the substrate. Fluorine-based gases, chlorine-based gases, etc., can be used to transfer the patterned organic film pattern onto the substrate through dry etching.
[0004] On the other hand, the miniaturization process in semiconductor device manufacturing is gradually approaching its inherent limit due to the wavelength of the light source used in photolithography. Therefore, in recent years, research has focused on the high integration of semiconductor devices that do not rely on miniaturization. As one method, semiconductor devices with complex structures such as multi-gate structures have been studied, and some have already been put into practical use. When forming such structures using a multilayer resist method, organic film-forming materials can be used to fill the micro-patterns such as holes, trenches, and fins formed on the substrate without gaps, or to fill uneven areas, densely patterned regions, and unpatterned areas with films, thereby achieving planarization. By using such organic film-forming materials to form a flat organic film surface on a substrate with unevenness, film thickness variations in the silicon-containing resist intermediate film and the resist upper film formed thereon can be suppressed, thus reducing the focal margin of the photolithography process and the margin reduction in subsequent substrate processing steps. This allows for the manufacture of semiconductor devices with good yield. On the other hand, in the single-layer resist method, in order to fill the substrate with height differences and patterns, the thickness of the upper resist film becomes thicker, which leads to the collapse of the pattern after exposure and development, and the deterioration of the pattern shape due to reflection from the substrate during exposure. The pattern formation margin during exposure becomes narrower, making it difficult to manufacture semiconductor devices with good yield.
[0005] Furthermore, as a method for achieving high speeds in next-generation semiconductor devices, research has begun on the application of novel materials with high electron mobility, such as strained silicon or gallium arsenide, and precision materials such as ultrathin polycrystalline silicon with angstrom-level control. However, when processing substrates using these novel precision materials, under conditions such as air at temperatures above 300°C, the planarization film is formed using organic film-forming materials, the material is corroded by oxygen in the air. This prevents the semiconductor device from achieving the performance required for high-speed production, potentially resulting in yields lower than those designed for industrial manufacturing. Therefore, to avoid yield reduction caused by substrate corrosion under such high-temperature air conditions, organic film-forming materials capable of forming films in inert gases are desired.
[0006] Previously, condensation resins obtained by using carbonyl compounds such as ketones and aldehydes, and aromatic alcohols as condensing agents to obtain phenolic and naphthol-based compounds were known as materials for forming organic films in multilayer resist methods. Examples include the fluorene-bisphenol phenolic varnish resin described in Patent Document 1, the bisphenol compound and its phenolic varnish resin described in Patent Document 2, the adamantane-phenol compound phenolic varnish resin described in Patent Document 3, and the bis-naphthol compound and its phenolic varnish resin described in Patent Document 4. These materials are formed into films with solvent resistance to coating film materials used in the next step through crosslinking by a hydroxymethyl compound as a crosslinking agent, oxidation of the α-position of the aromatic ring by the action of oxygen in the air, and subsequent curing by a condensation-based crosslinking reaction. However, the driving force for this solvent resistance is oxidation; therefore, sufficient heat resistance, flatness, and other properties cannot be satisfied in inert gases.
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Application Publication No. 2005-128509
[0010] Patent Document 2: Japanese Patent Application Publication No. 2006-293298
[0011] Patent Document 3: Japanese Patent Application Publication No. 2006-285095
[0012] Patent Document 4: Japanese Patent Application Publication No. 2010-122656 Summary of the Invention
[0013] The problem the invention aims to solve
[0014] The present invention was made in view of the above circumstances, and its object is to provide a compound capable of forming an organic film that cures not only under film-forming conditions in air but also under film-forming conditions in an inactive gas, exhibiting excellent heat resistance, pattern filling and planarization characteristics on a substrate, and good adhesion to the substrate, as well as an organic film forming material containing the compound. Furthermore, the present invention aims to provide a semiconductor device manufacturing substrate obtained using this material, a method for forming an organic film, and a pattern forming method.
[0015] Solution for solving the problem
[0016] To address the aforementioned issues, the present invention provides an organic film forming material, characterized in that it contains (A) an organic film forming compound represented by the following general formula (1A) and (B) an organic solvent.
[0017]
[0018] (In the formula, Y is an organic group with an n1 valence, a nitrogen atom with a trivalent valence, or a carbon atom with a tetravalent valence; n1 is an integer from 3 to 8; X is a partial structure shown in the following general formula (1B).)
[0019]
[0020] (In the formula, dashed lines represent connecting bonds. R1 and R2 represent halogen atoms, alkyl groups with 1 to 4 carbon atoms, alkoxy groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, or alkenyl groups with 2 to 4 carbon atoms. The hydrogen atoms on the carbon atoms constituting the aforementioned alkyl, alkoxy, alkynyl, or alkenyl groups may optionally be replaced by fluorine atoms. In addition, the aromatic rings that can be replaced by R1 may optionally form a bridging structure by means of a single bond or by means of a divalent group obtained by removing one hydrogen atom from the aforementioned R1. n4 and n5 represent integers from 0 to 2. Ar1 and Ar2 represent benzene rings or naphthalene rings, respectively. n2 represents 0 or 1, n3 represents 1 or 2, and R3 represents a hydrogen atom or an alkyl group with 1 to 4 carbon atoms, an alkynyl group with 2 to 4 carbon atoms, or an alkenyl group with 2 to 4 carbon atoms.)
[0021] If it is such an organic film forming material, then it becomes an organic film forming material that can form organic films that not only cure under film-forming conditions in air, but also under film-forming conditions in inactive gases, and has high heat resistance, good adhesion to the substrate, and high filling / planarization characteristics.
[0022] In this case, R3 in the aforementioned general formula (1B) is preferably any of the groups shown in the following formula (1C).
[0023]
[0024] (The dashed lines in the above formula represent connectors.)
[0025] From the viewpoint of imparting excellent curability, flatness, embedding properties, and adhesion to the substrate, it is preferable to introduce the aforementioned end structure into the organic film forming compound, which is component (A).
[0026] In addition, n1 in the aforementioned general formula (1A) is preferably 3 or 4.
[0027] It is preferable to adjust the number of substituents in the organic film-forming compound, which is component (A), to an appropriate range, from the viewpoint of preventing thermal fluidity from being impaired by rapid curing.
[0028] In addition, n2 in the aforementioned general formula (1B) is preferably 1.
[0029] By introducing the structure described above into the organic film-forming compound, which is component (A), the carbon density can be increased, thereby imparting etching resistance. Furthermore, heat-induced film shrinkage is suppressed, thus enabling the formation of a film with good heat resistance and flatness.
[0030] Furthermore, Y in the aforementioned general formula (1A) is preferably any of the partial structures shown in the following formula (1D).
[0031]
[0032] (The dashed lines in the above formula represent connecting bonds, and R4 represents a hydrogen atom or a methyl group.)
[0033] From the viewpoint that having the structure described above improves various physical properties such as heat resistance, solvent solubility, and flatness, the structure described above is preferred.
[0034] The ratio of the weight-average molecular weight Mw to the number-average molecular weight Mn of the aforementioned component (A) based on gel permeation chromatography is preferably 1.00 ≤ Mw / Mn ≤ 1.10.
[0035] By controlling the Mw / Mn ratio of the organic membrane-forming compound as component (A) within this range, it is possible to form an organic membrane with excellent landfill characteristics and flatness.
[0036] The organic solvent mentioned above (B) is preferably a mixture of one or more organic solvents with a boiling point below 180°C and one or more organic solvents with a boiling point above 180°C.
[0037] Organic film-forming materials, which are mixtures of organic solvents as described above, are endowed with thermal fluidity by the addition of high-boiling-point solvents, thereby enabling the provision of organic films with both superior landfill / planarization properties. It should be noted that, in this invention, the boiling point is a value at 1 atmosphere (1013 hPa).
[0038] In addition, the organic film forming material of the present invention may also contain one or more of (C) an acid-producing agent, (D) a surfactant, (E) a crosslinking agent and (F) a plasticizer.
[0039] The organic film forming material of the present invention may contain one or more of the components (C) to (F) mentioned above, depending on its purpose.
[0040] In addition, the present invention provides a substrate for manufacturing a semiconductor device, characterized in that an organic film obtained by curing the organic film forming material of the present invention is formed on the substrate.
[0041] This substrate contains an organic film that combines high heat resistance, good adhesion to the substrate, and high filling / planarization properties. Therefore, if used in the semiconductor device manufacturing process, the yield of semiconductor devices becomes good.
[0042] Furthermore, the present invention provides a method for forming an organic film, characterized in that it is a method for forming an organic film used in the manufacturing process of a semiconductor device, wherein the organic film forming material of the present invention is spin-coated onto a substrate to be processed, and the substrate to be processed coated with the organic film forming material is subjected to heat treatment in an inactive gas atmosphere at a temperature of 50°C or higher and 600°C or lower for a period of 5 seconds to 7200 seconds to obtain a cured film.
[0043] The organic film used in the manufacturing process of the semiconductor device formed by the method of the present invention will solidify even when film is formed in an inactive gas, and has high heat resistance and high packing / planarization characteristics. If used in the manufacturing process of the semiconductor device, the yield of the semiconductor device becomes good.
[0044] In addition, the present invention provides a method for forming an organic film, characterized in that it is a method for forming an organic film used in the manufacturing process of a semiconductor device, wherein the organic film forming material of the present invention is spin-coated onto a substrate to be processed, and the substrate to be processed coated with the organic film forming material is heat-treated in air at a temperature of 50°C or higher and 300°C or lower for a period of 5 to 600 seconds to form a coated film, and then heat-treated in an inert gas atmosphere at a temperature of 200°C or higher and 600°C or lower for a period of 10 to 7200 seconds to obtain a cured film.
[0045] The organic film used in the manufacturing process of the semiconductor device formed by the method of the present invention will solidify even if it is formed locally in an inactive gas, and has high heat resistance and high packing / planarization characteristics. If used in the manufacturing process of the semiconductor device, the yield of the semiconductor device becomes good.
[0046] Furthermore, in the method for forming the organic membrane of the present invention, it is preferable to set the oxygen concentration in the aforementioned inactive gas to 1% by volume or less.
[0047] If the organic film forming material of the present invention is used, it is possible to form an organic film that fully cures without producing sublimation even when heated in such an inert gas atmosphere, and exhibits excellent adhesion to the substrate. Furthermore, heating in such an inert gas atmosphere prevents corrosion of the processed substrate. It should be noted that in the present invention, oxygen concentration is expressed on a volume basis.
[0048] Furthermore, in this invention, the aforementioned substrate can be a structure with a height of 30 nm or more, or a substrate with a height difference.
[0049] The method for forming the organic film of the present invention is particularly useful for forming a flat organic film on such a processed substrate.
[0050] Furthermore, this invention provides a pattern forming method, characterized in that an organic film is formed on a workpiece using the organic film forming material of this invention, a silicon-containing photoresist intermediate film is formed on the organic film using a silicon-containing photoresist intermediate film material, a photoresist upper film is formed on the silicon-containing photoresist intermediate film using a photoresist composition, a circuit pattern is formed on the photoresist upper film, the pattern is transferred to the aforementioned silicon-containing photoresist intermediate film by etching using the pattern-formed photoresist upper film as a mask, the pattern is transferred to the aforementioned organic film by etching using the pattern-formed photoresist intermediate film as a mask, and further, the pattern is transferred to the aforementioned workpiece by etching using the pattern-formed organic film as a mask.
[0051] In addition, the present invention provides a pattern forming method, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention, a silicon-containing photoresist intermediate film is formed on the organic film using a silicon-containing photoresist intermediate film material, an organic antireflective film is formed on the silicon-containing photoresist intermediate film, and a photoresist upper film is formed on the organic antireflective film using a photoresist composition to form a photoresist upper film, thereby forming a four-layer film structure, forming a circuit pattern on the photoresist upper film, using the photoresist upper film with the pattern formed as a mask, transferring the pattern to the aforementioned organic antireflective film and the aforementioned silicon-containing photoresist intermediate film by etching, using the silicon-containing photoresist intermediate film with the transferred pattern as a mask, transferring the pattern to the aforementioned organic film by etching, and further, using the organic film with the transferred pattern as a mask, transferring the pattern to the aforementioned workpiece by etching.
[0052] In addition, the present invention provides a pattern forming method, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention, an inorganic hard mask selected from silicon oxide film, silicon nitride film, silicon nitride film, titanium oxide film, and titanium nitride film is formed on the organic film, a photoresist upper layer film is formed on the inorganic hard mask using a photoresist composition, a circuit pattern is formed on the photoresist upper layer film, the photoresist upper layer film with the pattern is used as a mask, the pattern is transferred to the aforementioned inorganic hard mask by etching, the pattern is transferred to the aforementioned organic film by etching using the inorganic hard mask with the transferred pattern as a mask, and further, the pattern is transferred to the aforementioned workpiece by etching using the organic film with the transferred pattern as a mask.
[0053] In addition, the present invention provides a pattern forming method, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention, an inorganic hard mask selected from silicon oxide film, silicon nitride film, silicon nitride film, titanium oxide film, and titanium nitride film is formed on the organic film, an organic antireflective film is formed on the inorganic hard mask, a photoresist top layer film is formed on the organic antireflective film using a photoresist composition to form a four-layer film structure, a circuit pattern is formed on the photoresist top layer film, the photoresist top layer film with the pattern is used as a mask, the pattern is transferred to the aforementioned organic antireflective film and the aforementioned inorganic hard mask by etching, the pattern is transferred to the aforementioned organic film by etching using the inorganic hard mask with the transferred pattern as a mask, and then the pattern is transferred to the aforementioned workpiece by etching using the organic film with the transferred pattern as a mask.
[0054] The organic film forming material of the present invention can be suitably used in various patterning methods, such as three-layer resist processes using silicon-containing resist interlayers or inorganic hard masks, and four-layer resist processes using organic anti-reflective films. In the manufacturing process of semiconductor devices, if circuit patterns are formed using this patterning method of the present invention, semiconductor devices can be manufactured with good yield.
[0055] When using the aforementioned inorganic hard mask, it is preferably formed by CVD or ALD.
[0056] In the pattern forming method of the present invention, an inorganic hard mask can be formed by, for example, this method.
[0057] Furthermore, in the present invention, in the formation of the aforementioned circuit pattern, it is preferable to form the circuit pattern by photolithography, direct electron beam drawing, nanoimprinting, or a combination thereof using light with a wavelength of 10 nm or more and 300 nm or less.
[0058] In the formation of the aforementioned circuit pattern, it is preferable to develop the circuit pattern using alkaline development or organic solvents.
[0059] In the pattern forming method of the present invention, such circuit pattern forming means and developing means can be suitably used.
[0060] Furthermore, as the aforementioned workpiece, it is preferable to use a semiconductor device substrate or a workpiece on which any one of a metal film, metal carbide film, metal oxide film, metal nitride film, metal oxide carbide film, and metal nitride film is formed.
[0061] As the aforementioned workpiece, it is preferred to use a workpiece containing silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or alloys thereof.
[0062] If it is the pattern forming method of the present invention, then the workpiece described above can be processed to form a pattern.
[0063] In addition, in this invention, a compound represented by the following general formula (1A) is provided.
[0064]
[0065] (In the formula, Y is an organic group with an n1 valence, a nitrogen atom with a trivalent valence, or a carbon atom with a tetravalent valence, n1 is an integer from 3 to 8, and X is a partial structure shown in the following general formula (1B).)
[0066]
[0067] (In the formula, dashed lines represent connecting bonds. R1 and R2 represent halogen atoms, alkyl groups with 1 to 4 carbon atoms, alkoxy groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, or alkenyl groups with 2 to 4 carbon atoms. The hydrogen atoms on the carbon atoms constituting the aforementioned alkyl, alkoxy, alkynyl, or alkenyl groups may optionally be replaced by fluorine atoms. In addition, the aromatic rings that can be replaced by R1 may optionally form a bridging structure by means of a single bond or by means of a divalent group obtained by removing one hydrogen atom from the aforementioned R1. n4 and n5 represent integers from 0 to 2. Ar1 and Ar2 represent benzene rings or naphthalene rings, respectively. n2 represents 0 or 1, n3 represents 1 or 2, and R3 represents a hydrogen atom or an alkyl group with 1 to 4 carbon atoms, an alkynyl group with 2 to 4 carbon atoms, or an alkenyl group with 2 to 4 carbon atoms.)
[0068] Compounds containing three or more Cardo structures in a single molecule can form organic films that cure not only under air-based film-forming conditions but also under inert gas-based film-forming conditions, exhibiting high heat resistance, good adhesion to substrates, and excellent packing / planarization properties, through the introduction of substituents into the terminal structures. Furthermore, by introducing multiple Cardo structures into the molecule, the crystallinity of the compound can be reduced, and its solubility in solvents can be improved without compromising heat resistance; thus, the seemingly contradictory properties of thermal fluidity and heat resistance can be balanced.
[0069] In this case, R3 in the aforementioned general formula (1B) is preferably any of the groups shown in the following formula (1C).
[0070]
[0071] (The dashed lines in the above formula represent connectors.)
[0072] By introducing this end structure, it is possible to exhibit cross-linking properties, good adhesion to the substrate, and high packing / planarization characteristics.
[0073] Regarding the compounds of the present invention, n1 in the aforementioned general formula (1A) is preferably 3 or 4.
[0074] It is preferable to adjust the number of substituents in the compound to an appropriate range, from the viewpoint of preventing thermal fluidity from being impaired by rapid curing.
[0075] In addition, n2 in the aforementioned general formula (1B) is preferably 1.
[0076] By introducing the structure described above into the compound, the carbon density can be increased, thereby imparting etch resistance. Furthermore, heat-induced film shrinkage is suppressed, thus enabling the formation of a film with good heat resistance and flatness.
[0077] Furthermore, Y in the aforementioned general formula (1A) is preferably any of the partial structures shown in the following formula (1D).
[0078]
[0079] (The dashed lines in the above formula represent connecting bonds, and R4 represents a hydrogen atom or a methyl group.)
[0080] From the viewpoint of improving various physical properties such as heat resistance, solvent solubility, and flatness, the compounds of the present invention are preferably configured as described above.
[0081] The effects of the invention
[0082] In summary, the compound of the present invention is useful for forming organic films that solidify without producing byproducts even when formed in an inert gas that prevents substrate corrosion, and possesses high heat resistance, good adhesion to the substrate, and high packing and planarization properties. Furthermore, organic film forming materials containing this compound (organic film forming compound) become materials for forming organic films with excellent packing / planarization properties, as well as heat resistance, etching resistance, and other properties. Therefore, if an organic film is obtained using the organic film forming material of the present invention, it possesses high packing / planarization properties, thus forming an organic film free from micropores caused by poor packing and uneven organic film surfaces caused by insufficient planarity. Therefore, the organic film forming material of the present invention is extremely useful as an organic film forming material in multilayer photoresist methods such as the two-layer photoresist method, the three-layer photoresist method using a silicon-containing interlayer film, and the four-layer photoresist method using a silicon-containing interlayer film and an organic antireflective film, or as a planarization material for semiconductor device manufacturing. Furthermore, the organic film formed from the organic film forming material of the present invention exhibits excellent heat resistance. Therefore, even when a CVD hard mask is formed on the organic film, the film thickness will not change due to thermal decomposition, making it suitable for patterning. Moreover, the semiconductor device substrate planarized using the organic film of the present invention has a larger process margin during patterning, enabling the manufacture of semiconductor devices with good yield. Furthermore, if the patterning method of the present invention is used to form circuit patterns during the semiconductor device manufacturing process, semiconductor devices can be manufactured with good yield. Attached Figure Description
[0083] Figure 1 This is an illustration of the flattening characteristics in this invention.
[0084] Figure 2 This is an illustrative diagram illustrating an example of a pattern formation method based on the three-layer resist method of the present invention.
[0085] Figure 3 This is an explanatory diagram of the landfill characteristic evaluation method in the embodiments.
[0086] Figure 4 This is an illustrative diagram of the flattening characteristic evaluation method in the embodiments.
[0087] Figure 5 This is an illustrative diagram illustrating the fit measurement method in the examples.
[0088] Explanation of reference numerals in the attached figures
[0089] 1…substrate, 2…processed layer, 2a…pattern formed on the processed layer, 3…organic film, 3a…organic film pattern, 3'…material for forming organic film, 4…silicon-containing photoresist intermediate film, 4a…silicon-containing photoresist intermediate film pattern, 5…photoresist upper layer film, 5a…photoresist upper layer film pattern, 6…used portion (exposed portion), 7…substrate with dense hole pattern, 8…organic film, 9…substrate with large isolated trench pattern, 10…organic film, delta 10…thickness difference of photoresist intermediate film between trench portion and non-trench portion, 11…silicon wafer, 12…cured coating, 13…aluminum pin with adhesive, 14…support stage, 15…clamp, 16…stretching direction. Detailed Implementation
[0090] As described above, in order to prevent substrate corrosion, there is a need to develop organic film forming compounds that can be formed under film-forming conditions in an inactive gas environment, for example at temperatures above 300°C, without producing byproducts, and that not only exhibit excellent pattern-filling and planarization characteristics on the substrate, but also good resistance to dry etching during substrate processing. Furthermore, there is a need to develop organic film forming materials that do not cause film thickness variations due to thermal decomposition when forming CVD hard masks on such organic films, and organic film forming compounds that are useful for pattern forming methods using such materials.
[0091] Typically, in forming an organic film, an organic film-forming compound is dissolved in an organic solvent to prepare a composition, which is then coated onto a substrate on which a semiconductor device structure, wiring, etc., is formed, and calcined to form an organic film. Immediately after coating, the coating film forms along the shape of the uneven structure on the substrate. However, during calcination of this coating film, most of the organic solvent evaporates until curing occurs, and the organic film is formed using the organic film-forming compound remaining on the substrate. The inventors conceived that if the organic film-forming compound remaining on the substrate at this time has sufficient thermal fluidity, the uneven shape immediately after coating can be flattened through thermal flow, forming a flat film.
[0092] Through further repeated and in-depth research, the inventors discovered that if the organic film-forming compound is an organic film-forming compound with fluorene substituents as shown in the following general formula (1A), then, by means of the substituents introduced to the end, it exhibits thermosetting properties comparable to conventional organic film-forming materials not only in air but also in inert gases, with good thermal fluidity, thus demonstrating excellent packing / planarization characteristics. Because it undergoes a curing mechanism independent of oxidation, its etch resistance does not deteriorate due to oxidation of the organic film-forming compound, exhibiting excellent dry etching resistance. Furthermore, due to the presence of multiple rigid fluorene structures, it is possible to provide an organic film-forming material that also possesses heat resistance, preventing coating thickness variations due to thermal decomposition, even when forming a CVD hard mask, thus completing the present invention.
[0093] That is, the present invention is an organic film forming material, characterized in that it contains (A) an organic film forming compound represented by the following general formula (1A) and (B) an organic solvent.
[0094]
[0095] (In the formula, Y is an organic group with an n1 valence, a nitrogen atom with a trivalent valence, or a carbon atom with a tetravalent valence, n1 is an integer from 3 to 8, and X is a partial structure shown in the following general formula (1B).)
[0096]
[0097] (In the formula, dashed lines represent connecting bonds. R1 and R2 represent halogen atoms, alkyl groups with 1 to 4 carbon atoms, alkoxy groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, or alkenyl groups with 2 to 4 carbon atoms. The hydrogen atoms on the carbon atoms constituting the aforementioned alkyl, alkoxy, alkynyl, or alkenyl groups may optionally be replaced by fluorine atoms. In addition, the aromatic rings that can be replaced by R1 may optionally form a bridging structure by means of a single bond or by means of a divalent group obtained by removing one hydrogen atom from the aforementioned R1. n4 and n5 represent integers from 0 to 2. Ar1 and Ar2 represent benzene rings or naphthalene rings, respectively. n2 represents 0 or 1, n3 represents 1 or 2, and R3 represents a hydrogen atom or an alkyl group with 1 to 4 carbon atoms, an alkynyl group with 2 to 4 carbon atoms, or an alkenyl group with 2 to 4 carbon atoms.)
[0098] In addition, the present invention provides a compound represented by the above general formula (1A), which can be used as a material for forming organic films.
[0099] The present invention will now be described in detail, but it is not limited thereto.
[0100] The organic film forming material of the present invention is characterized in that it contains an organic film forming compound (component A) represented by the above general formula (1A) and an organic solvent (component B). This organic film forming material only needs to contain the compound (organic film forming compound) represented by the above general formula (1A) and an organic solvent, and may contain other components as needed. The components will be described below.
[0101] <Compounds for Organic Film Formation>
[0102] The organic film forming compound of the present invention is an organic film forming compound represented by the following general formula (1A).
[0103]
[0104] (In the formula, Y is an organic group with an n1 valence, a nitrogen atom with a trivalent valence, or a carbon atom with a tetravalent valence, n1 is an integer from 3 to 8, and X is a partial structure shown in the following general formula (1B).)
[0105]
[0106] (In the formula, dashed lines represent connecting bonds. R1 and R2 represent halogen atoms, alkyl groups with 1 to 4 carbon atoms, alkoxy groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, or alkenyl groups with 2 to 4 carbon atoms. The hydrogen atoms on the carbon atoms constituting the aforementioned alkyl, alkoxy, alkynyl, or alkenyl groups may optionally be replaced by fluorine atoms. In addition, the aromatic rings that can be replaced by R1 may optionally form a bridging structure by means of a single bond or by means of a divalent group obtained by removing one hydrogen atom from the aforementioned R1. n4 and n5 represent integers from 0 to 2. Ar1 and Ar2 represent benzene rings or naphthalene rings, respectively. n2 represents 0 or 1, n3 represents 1 or 2, and R3 represents a hydrogen atom or an alkyl group with 1 to 4 carbon atoms, an alkynyl group with 2 to 4 carbon atoms, or an alkenyl group with 2 to 4 carbon atoms.)
[0107] By introducing three or more Cardo structures into the molecule as shown in the general formula (1B) above, the crystallinity of the compound can be reduced, and its solubility in solvents can be improved without compromising its heat resistance, thus achieving a balance between the trade-offs of thermal fluidity and heat resistance. Furthermore, regarding OR3, curability can be imparted in the atmosphere and inactive gases by selecting substituents, and the chain length can be appropriately adjusted from the viewpoints of imparting flatness and curability. Additionally, by mixing with compounds containing ether or hydroxyl groups locally, high adhesion to the substrate can be achieved. Furthermore, by appropriately selecting the structure forming the main framework as shown in Y, various physical properties such as etching resistance and optical properties can be adjusted. These compounds can prevent film peeling when an inorganic hard mask is formed directly above an organic film using CVD or ALD methods, resulting in organic films with excellent process margins.
[0108] In the Y of the above general formula (1A), the following groups can be cited as examples of organic groups with an n1 valence. When these aromatic rings are present, the groups optionally having substituents can be cited as alkyl groups with 1 to 10 carbon atoms, alkynyl and alkenyl groups with 3 to 10 carbon atoms, aryl groups with 6 to 10 carbon atoms, nitro groups, halogen groups, nitrile groups, alkoxycarbonyl groups with 1 to 10 carbon atoms, alkanoyloxy groups with 1 to 10 carbon atoms, etc.
[0109]
[0110]
[0111]
[0112]
[0113] Among the compounds represented by the above general formula (1A), examples of bridging structures formed by substituent R1 on the aromatic ring of general formula (1B) replacing hydrogen atoms in other aromatic rings (R1 of other aromatic rings bonded to each other to form a bridging structure) can be shown below. Ar1, Ar2, n1, n2, n3, n5, R1, R2, and R3 are the same as those described above.
[0114]
[0115] Of the above, from the viewpoint of adjusting the number of substituents in the compound to an appropriate range to prevent damage to thermal fluidity due to rapid curing, and from the viewpoint that the increase in the molecular weight of the compound due to the increase of the substituents shown by X will lead to damage to thermal fluidity, it is preferred to satisfy n1=3 or 4, that is, Y is a trivalent or tetravalent organic group. From the perspective of the ease of obtaining raw materials, n1=3 is more preferred.
[0116] Furthermore, from the viewpoints of ease of obtaining raw materials, heat resistance, and thermal fluidity, Y is more preferably any of the partial structures shown in the following formula (1D).
[0117]
[0118] (The dashed lines in the above formula represent connecting bonds, and R4 represents a hydrogen atom or a methyl group.)
[0119] In the above general formula (1A), X is the same as the following general formula (1B).
[0120]
[0121] (In the formula, dashed lines represent connecting bonds. R1 and R2 represent halogen atoms, alkyl groups with 1 to 4 carbon atoms, alkoxy groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, or alkenyl groups with 2 to 4 carbon atoms. The hydrogen atoms on the carbon atoms constituting the aforementioned alkyl, alkoxy, alkynyl, or alkenyl groups may optionally be replaced by fluorine atoms. In addition, the aromatic rings that can be replaced by R1 may optionally form a bridging structure by means of a single bond or by means of a divalent group obtained by removing one hydrogen atom from the aforementioned R1. n4 and n5 represent integers from 0 to 2. Ar1 and Ar2 represent benzene rings or naphthalene rings, respectively. n2 represents 0 or 1, n3 represents 1 or 2, and R3 represents a hydrogen atom or an alkyl group with 1 to 4 carbon atoms, an alkynyl group with 2 to 4 carbon atoms, or an alkenyl group with 2 to 4 carbon atoms.)
[0122] As part of the structure shown in the above general formula (1B), the following partial structures can be exemplified. R1, R2, R3, n3, n4, and n5 are the same as those described above.
[0123]
[0124]
[0125]
[0126]
[0127]
[0128] As part of the structure represented by Ar1 and Ar2 in the above general formula (1B), it is preferred that Ar1 and Ar2 are benzene rings; or that Ar1 and Ar2 are a combination of benzene rings and naphthalene rings. When Ar1 and Ar2 are benzene rings, from a symmetry point of view, improved heat resistance can be expected. When Ar1 and Ar2 are a combination of benzene rings and naphthalene rings, an asymmetric structure is presented, which can further improve the solubility of the compound in solvents. From the perspective of ease of obtaining raw materials, it is more preferable that Ar1 and Ar2 are benzene rings.
[0129] In the above general formula (1B), the substituents R1 and R2 on the aromatic group can respectively represent halogen atoms such as fluorine, chlorine, bromine, and iodine; alkyl groups with 1 to 4 carbon atoms such as methyl, ethyl, propyl, isopropyl, butyl, sec-butyl, and tert-butyl; alkoxy groups with 1 to 4 carbon atoms such as methoxy, ethoxy, propyloxy, n-butoxy, sec-butoxy, and tert-butoxy; alkenyl groups with 2 to 4 carbon atoms such as vinyl, allyl, and butenyl; and alkynyl groups with 2 to 4 carbon atoms such as ethynyl, propynyl, and butynyl. Some or all of the hydrogen atoms on the carbon atoms of the alkoxy, alkyl, alkenyl, and alkynyl groups may be optionally replaced by fluorine substituents such as fluorine atoms. For example, if it is methyl, trifluoromethyl, difluoromethyl, monofluoromethyl, etc. are formed. Among these, from the viewpoint of heat resistance and etching resistance, n4 and n5 = 0 are preferred; from the viewpoint of flatness and solubility, R1 is preferably trifluoromethyl.
[0130] In the above general formula (1B), R3 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, an alkynyl group having 2 to 4 carbon atoms, or an alkenyl group. Examples of alkyl groups having 1 to 4 carbon atoms include methyl, ethyl, propyl, isopropyl, butyl, sec-butyl, and tert-butyl. Examples of alkenyl groups having 2 to 4 carbon atoms include vinyl, allyl, and butenyl. Examples of alkynyl groups having 2 to 4 carbon atoms include ethynyl, propynyl, and butynyl. Among these, the structure shown in (1C) below is preferred, and propynyl is more preferred from the viewpoint of thermosetting.
[0131]
[0132] In the above general formula (1B), n2 is an integer of 0 or 1. From the viewpoint of heat resistance and etching resistance, n2 = 1 is preferred, that is, naphthalene ring is preferred.
[0133] In the above general formula (1B), n3 is an integer of 1 or 2. From the viewpoint of curability, n3 = 2 is preferred, especially when the substituent represented by -OR3, similar to catechol, is adjacent, as in the partial structure described below, which is particularly preferred from the viewpoint of adhesion and heat resistance.
[0134]
[0135] Furthermore, in the above general formula (1B), as described below, it is preferable that n2 = 1 and n3 is an integer of 1 or 2. From the viewpoint of curability, it is more preferable that n3 = 2. In particular, when the substituent represented by -OR3, similar to catechol, is adjacent as in the partial structure described below, it is especially preferred from the viewpoint of adhesion and heat resistance.
[0136]
[0137] Furthermore, it can be considered that when the partial structure with the substituent shown in OR3 has a propoxy group at the β-position of the naphthalene ring as shown below, the propoxy group, after forming a cyclized body through baking, exhibits thermosetting properties through polymerization. In this case, the propoxy group imparts fluidity before cyclization and, after cyclization, not only functions as a curing group but also contributes to improved heat resistance by forming a ring structure. In this curing reaction, no decompositional additives such as thermally generated acidic agents that form gaseous components, or byproducts such as condensation reactions are generated. Therefore, both sublimation components during baking and film shrinkage can be suppressed. Through these effects, heat resistance and landfill / planarization characteristics, which are opposite properties, can be simultaneously achieved, making this method further preferred.
[0138]
[0139] Furthermore, in the structure constituting R3, if the proportion of hydrogen atoms is set as 'a', and the proportion of alkyl groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, and alkenyl groups are set as 'b', the proportions of hydrogen atoms that are expected to impart adhesion and film-forming properties to the substrate, and the proportions of alkyl groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, and alkenyl groups that are expected to impart heat resistance and thermal fluidity can be adjusted arbitrarily according to the desired performance. When adjusted to an arbitrary proportion, the substituent introduction rate can be adjusted by reaction, or a compound in which R3 is hydrogen atoms and a compound in which R3 is substituted by alkyl groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, and alkenyl groups can be prepared separately, mixed, and adjusted to the desired proportion.
[0140] Furthermore, the ratio of the weight-average molecular weight Mw to the number-average molecular weight Mn of the compound represented by general formula (1A) based on gel permeation chromatography (GPC), Mw / Mn, is preferably 1.00 ≤ Mw / Mn ≤ 1.10. By definition, if it is a monomolecular compound, Mw / Mn is 1.00, but depending on the separation properties of gel permeation chromatography, the measured value sometimes exceeds 1.00. Generally, for polymers with repeating units, Mw / Mn is extremely difficult to approach 1.00 unless a special polymerization method is used, and for distributions with Mw, Mw / Mn becomes a value exceeding 1. In this invention, to distinguish between monomolecular compounds and polymers, the index representing monomolecularity is defined as 1.00 ≤ Mw / Mn ≤ 1.10. It should be noted that the average molecular weight and dispersity in this invention are the weight-average molecular weight (Mw), number-average molecular weight (Mn), and dispersity (Mw / Mn) converted from polystyrene, measured by GPC using tetrahydrofuran as the eluent.
[0141] By controlling the Mw / Mn ratio of the compounds in the organic membrane forming composition within this range, it is possible to form organic membranes with excellent landfill characteristics and flatness.
[0142] [Method for manufacturing compounds for organic film formation]
[0143] As an example of a method for manufacturing the compound represented by general formula (1A) of the present invention, a method for obtaining the target product by means of the following steps can be illustrated: a step (step 1) in which an organometallic reagent having metal M is added to a ketone having Ar1 or Ar2 to obtain a fluorene alcohol as an intermediate; followed by a dehydration condensation reaction using an acid catalyst with benzene or naphthalene having OR3 as a substituent as a starting material (step 2). The reactions used in steps 1 and 2 can use one or more starting materials, which can be appropriately combined according to the desired characteristics.
[0144] Step 1
[0145] Step 2
[0146]
[0147] (In the above formula, Y, Ar1, Ar2, n1, n2, n3, n4, n5, R1, R2, and R3 are the same as those mentioned above, M represents metals such as Li and MgX1, and X1 represents halogen atoms.)
[0148] Examples of organometallic reagents used in step 1 include Grignard reagents, organolithium reagents, organozinc reagents, and organotitanium reagents, with Grignard reagents and organolithium reagents being particularly preferred. Grignard reagents and organolithium reagents can be prepared by direct metallization of the corresponding halides with metallic magnesium or metallic lithium, or by metal-halogen exchange reactions with aliphatic organometallic compounds such as isopropyl magnesium halide, methyllithium, and butyllithium.
[0149] In addition, organozinc and organotitanium reagents can be prepared by reacting corresponding Grignard or organolithium reagents with zinc halides, titanium halides (IV), alkoxytitanium (IV), etc. Metal salt compounds may coexist during the preparation of the above organometallic reagents or during their reaction with tricyclopentadienyltriphenylene oxide (Sumanene). In this case, transition metal catalysts such as palladium and nickel are used for the reaction.
[0150] Examples of the aforementioned metal salt compounds include cyanides, halides, and perhalates. Preferred metal salt compounds include lithium salts such as lithium chloride, lithium bromide, lithium iodide, and lithium perchlorate; and copper salts such as copper cyanide (I), copper cyanide (II), copper chloride (I), copper chloride (II), and dilithium tetrachlorocuprate.
[0151] By adding the aforementioned metal salt compound in an amount of 0.01 to 5.0 equivalents, preferably 0.2 to 2.0 equivalents, relative to the organometallic reagent, the solubility of the organometallic reagent can be increased, making it easier to prepare. In addition, the nucleophilicity and Lewis acidity of the reagent can be adjusted.
[0152] As solvents used in the preparation of the above-mentioned organometallic reagents and in the reaction with tricyclopentadienetriphenylene oxide, ethers such as diethyl ether, dibutyl ether, tetrahydrofuran, 1,4-dioxane, and cyclopentylmethyl ether can be used alone or in combination; hydrocarbons such as benzene, toluene, xylene, mesitylene, hexane, heptane, octane, and isooctane can be used; and nonprotic polar solvents such as N,N,N',N'-tetramethylethylenediamine, hexamethylphosphoric triamide, and N,N-dimethylformamide can be used.
[0153] The reaction temperature depends on the type of ketone or organometallic reagent containing Ar1 or Ar2, and the reaction conditions, preferably -70 to 150°C. For example, when the organometallic reagent is an organozinc reagent or a Grignard reagent, the reaction can be carried out under reflux at room temperature to the solvent boiling point, etc., and various options can be made depending on the reaction. Regarding the reaction time, it is generally preferred to carry out the reaction for 30 minutes to 48 hours.
[0154] As reaction methods, there are methods such as: adding a pre-prepared organometallic reagent and a ketone having Ar1 and Ar2 together to a solvent; or dispersing or dissolving one of the organometallic reagent and the ketone having Ar1 and Ar2 in a solvent, and then adding the other one that has been dispersed or dissolved in the solvent dropwise. The resulting intermediate fluorene alcohol can be quenched by using water or the like, and then proceeded as is in step 2 with the dehydration condensation reaction. In order to remove unreacted raw materials, catalysts, etc., present in the system as reaction intermediates, it can also be diluted to an organic solvent and then recovered in powder form by separation washing and crystallization in a poor solvent.
[0155] As the acid catalyst used in the dehydration condensation reaction shown in step 2, inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropoly acids can be used; organic acids such as oxalic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid can be used; and Lewis acids such as aluminum trichloride, aluminum ethoxide, aluminum isopropoxide, boron trifluoride, boron trichloride, boron tribromide, tin tetrachloride, tin tetrabromide, dibutyltin dichloride, dibutyltin dimethoxide, dibutyltin oxide, titanium tetrachloride, titanium tetrabromide, titanium methoxide (IV), titanium ethoxide (IV), titanium isopropoxide (IV), and titanium oxide (IV) can be used. The amount of these catalysts relative to the molar amount of the intermediate fluorene alcohol can be in the range of 0.1 to 20 moles, preferably 0.2 to 10 moles.
[0156] The solvents used are not particularly limited, but examples include alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether; ethers such as diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane; chlorinated solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene; hydrocarbons such as hexane, heptane, benzene, toluene, xylene, and cumene; nitriles such as acetonitrile; ketones such as acetone, ethyl methyl ketone, and isobutyl methyl ketone; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; and aprotic polar solvents such as dimethyl sulfoxide, N,N-dimethylformamide, and hexamethylphosphoric triamide. These solvents can be used alone or in combination of two or more. These solvents can be used in the range of 0 to 2000 parts by mass relative to 100 parts by mass of the reactants. The preferred reaction temperature is around -50°C to the boiling point of the solvent, and more preferably room temperature to 150°C. The reaction time can be appropriately selected from 0.1 to 100 hours.
[0157] The reaction methods include: adding fluorene alcohols, benzene, or naphthalene together with an acid catalyst; dispersing or dissolving fluorene alcohols, benzene, or naphthalene, and then adding the catalyst either together or in batches, or diluting with a solvent and adding dropwise; or dispersing or dissolving the catalyst, and then adding fluorene alcohols, benzene, or naphthalene separately either together or in batches, or diluting with a solvent and adding dropwise. In this case, depending on the reactivity of benzene or naphthalene, when fluorene alcohol is 1 mole, it is preferable to use 2 moles or more of benzene or naphthalene. After the reaction is complete, to remove the catalyst used in the reaction, the target substance can be recovered by liquid-liquid washing after dilution in an organic solvent.
[0158] The organic solvent used at this stage is not particularly limited as long as it can dissolve the target substance and separates into two layers even when mixed with water. Examples include hydrocarbons such as hexane, heptane, benzene, toluene, and xylene; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; ketones such as methyl ethyl ketone, methyl pentyl ketone, cyclohexanone, and methyl isobutyl ketone; ethers such as diethyl ether, diisopropyl ether, methyl tert-butyl ether, and ethylcyclopentyl methyl ether; chlorinated solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene; and mixtures thereof. The cleaning water used at this stage can be water commonly referred to as deionized water or ultrapure water. The number of cleaning cycles only needs to be one or more. Since even cleaning more than ten times may not necessarily achieve a cumulative cleaning effect, one to five cycles are preferred.
[0159] In liquid-liquid separation cleaning, alkaline aqueous solutions can be used to remove acidic components from the system. Specifically, examples of alkalis include alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates, ammonia, and organic ammonium compounds.
[0160] Furthermore, during the separation and cleaning process, acidic aqueous solutions can be used to remove metallic impurities or alkaline components from the system. Specifically, acids include inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropoly acids; and organic acids such as oxalic acid, fumaric acid, maleic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid.
[0161] The separation and cleaning based on the above-mentioned alkaline and acidic aqueous solutions can be performed using only one or a combination of them. From the viewpoint of removing metallic impurities, separation and cleaning is preferably performed in the order of alkaline and acidic aqueous solutions.
[0162] After separation and cleaning using the aforementioned alkaline and acidic aqueous solutions, neutral water can be used for subsequent cleaning. Cleaning only once or more is sufficient, preferably 1 to 5 times. For the neutral water, deionized water or ultrapure water as described above can be used. Cleaning only once or more is sufficient; fewer cleansing times may not remove alkaline or acidic components. Even cleaning more than 10 times may not achieve a cumulative cleaning effect; therefore, 1 to 5 cleansing times are preferred.
[0163] Furthermore, the reaction products after the liquid-liquid separation operation can be recovered in powder form by concentrating and drying the solvent or crystallizing it under reduced pressure or normal pressure. To improve the operability when preparing materials for organic film formation, a solution of appropriate concentration can also be prepared in advance. The preferred concentration is 0.1–50% by mass, more preferably 0.5–30% by mass. At this concentration, the viscosity is unlikely to increase, thus preventing impairment of operability. Additionally, the amount of solvent is not excessive, making it economical.
[0164] As a solvent at this time, there are no particular limitations as long as it can dissolve the compound. Specific examples include ketones such as cyclohexanone and methyl-2-pentyl ketone; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol; ethers such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; and esters such as propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol monotert-butyl ether acetate. These can be used alone or in combination of two or more.
[0165] [Other methods for manufacturing the compound]
[0166] Furthermore, when the R3 of the compound represented by the above general formula (1A) used in the organic film forming material of the present invention is not a hydrogen atom, other manufacturing methods can be listed as a step involving the following steps: obtaining an intermediate by using a fluorene alcohol as shown below in a dehydration condensation reaction with an acid catalyst using a hydroxyl-containing benzene or naphthalene, so-called phenol or naphthol as a raw material (step 1-1). A monomolecular compound can be obtained by using a raw material represented by R3-X2 having a leaving group X2 that converts the hydroxyl group to OR3 and performing a substitution reaction using a base catalyst (step 2-1). In this case, one or more R3-X2s can be used, and the ratio of hydroxyl to OR3 can be controlled by controlling the reaction rate. By locally introducing a polar structure such as a hydroxyl group, the film-forming properties and the adhesion of the film to the substrate can also be controlled.
[0167] Step 1-1
[0168]
[0169] Step 2-1
[0170]
[0171] (In the above formula, Y, Ar1, Ar2, n1, n2, n3, n4, n5, R1, R2, and R3 are the same as those mentioned above, and X2 represents a halogen atom, toluenesulfonate, or methanesulfonate.)
[0172] The dehydration condensation reaction in step 1-1 can be carried out by the method described in the method for manufacturing the compound of general formula (1A) above. Regarding the reaction method and the method for recovering the compound, they can be carried out by the method described in the method for manufacturing the compound of general formula (1A) above.
[0173] As base catalysts used in the substitution reaction (step 2-1), examples include inorganic base compounds such as sodium bicarbonate, sodium carbonate, potassium carbonate, calcium carbonate, cesium carbonate, sodium hydroxide, potassium hydroxide, sodium hydride, and potassium phosphate; and organic amine compounds such as triethylamine, pyridine, and N-methylmorpholine. They can be used alone or in combination of two or more.
[0174] There are no particular limitations on the solvents used at this time, as long as they are inactive for the above reaction. For example, ether solvents such as diethyl ether, tetrahydrofuran, and dioxane; aromatic solvents such as benzene, toluene, and xylene; acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, and water can be used alone or in combination.
[0175] The reaction method and the method for recovering the compound can be carried out by the method described in the method for manufacturing the compound shown in the above general formula (1A).
[0176] In the preparation of compounds used in organic film-forming materials obtained by this method, various halides, toluenesulfonates, and methanesulfonates can be used alone or in combination, depending on the required performance. For example, substances with side-chain structures that contribute to improved planarization properties, rigid aromatic ring structures that contribute to etch resistance and heat resistance, can be combined in any proportion. Therefore, organic film-forming materials obtained using these compounds can achieve a high level of balance between landfill / planarization properties and etch resistance.
[0177] As described above, if it is the organic film forming compound of the present invention, it can provide an organic film forming material that can be formed in a non-reactive gas that prevents substrate corrosion and also solidifies without producing byproducts, has good adhesion to the substrate, and also has, for example, heat resistance of 400°C or higher and high packing / planarization characteristics.
[0178] It should be noted that, in this invention, planarization characteristics refer to the property of planarizing the surface of a substrate. If the material (composition) contains the organic film-forming compound of this invention, then for example, like... Figure 1 As shown, by coating an organic film forming material 3' onto a substrate 1 and heating it to form an organic film 3, the height difference of 100 nm in the substrate 1 can be reduced to below 30 nm. It should be noted that... Figure 1 The elevation difference shape shown represents a typical example of the elevation difference shape in a substrate for manufacturing semiconductor devices. Naturally, the elevation difference shape of a substrate that can be planarized using a material containing the organic film forming compound of the present invention is not limited to this.
[0179] Materials for Organic Film Formation
[0180] Furthermore, this invention provides an organic film-forming material comprising (A) the organic film-forming compound of the present invention described above and (B) an organic solvent. It should be noted that in the organic film-forming material of the present invention, the organic film-forming compound of the present invention can be used alone or in combination of two or more. Additionally, the organic film-forming material of the present invention may also be referred to as an organic film-forming composition.
[0181] Furthermore, in this invention, as described above, a method can be employed that uses only two or more substituents represented by R3 to actively control the substituent introduction rate in a manner that presents the desired performance, specifically targeting the proportion of substituent R3. Specifically, the following method can be employed: in the structure constituting R3 of the compound, when the proportion of hydrogen atoms is set as a, and the proportion of alkyl groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, and alkenyl groups are set as b, the proportions of hydrogen atoms that are expected to impart adhesion and film-forming properties to the substrate, and the proportions of alkyl groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, and alkenyl groups that are expected to impart heat resistance and thermal fluidity are adjusted in any ratio. Based on the desired performance, the substituent introduction rate is adjusted such that the proportion of b is a + b = 100 (%). When controlling the substituent introduction rate, the desired compound can be obtained by reacting a compound having one or more leaving groups X2 using the method described in [Other Methods for Manufacturing Compounds].
[0182] <Organic solvents>
[0183] As for the organic solvent that can be used in the organic film forming material of the present invention, there are no particular limitations as long as it dissolves the aforementioned organic film forming compound of the present invention, as well as optional components such as acid-generating agents, crosslinking agents, and other additives. Specifically, solvents with a boiling point below 180°C, such as those described in paragraphs (0091) to (0092) of Japanese Patent Application Publication No. 2007-199653, can be used. Among these, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, 2-heptanone, cyclopentanone, cyclohexanone, and mixtures of two or more thereof are preferred.
[0184] If it is such a material, it can be coated by spin coating. In addition, since it contains the organic film forming compound of the present invention as described above, it becomes an organic film forming material that has both heat resistance of over 400°C and high landfill / planarization properties.
[0185] Furthermore, in the organic film-forming material of the present invention, as an organic solvent, a high-boiling-point solvent (a mixture of a solvent with a boiling point below 180°C and a solvent with a boiling point above 180°C) can also be added to the solvent with a boiling point below 180°C. As a high-boiling-point organic solvent, it is not particularly limited to hydrocarbons, alcohols, ketones, esters, ethers, chlorinated solvents, etc., as long as it can dissolve the organic film-forming compound. Specific examples include 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecaneol, ethylene glycol, 1,2-propanediol, 1,3-butanediol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-hexanediol, and diethylene glycol. Dipropylene glycol, triethylene glycol, tripropylene glycol, glycerol, n-nonyl acetate, ethylene glycol monohexyl ether, ethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, diethylene glycol monohexyl ether, diethylene glycol monophenyl ether, diethylene glycol monobenzyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ... Alcohol monomethyl ether, triethylene glycol n-butyl ether, triethylene glycol butyl methyl ether, triethylene glycol diacetate, tetraethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol mono-n-butyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, Triacetin, propylene glycol diacetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol methyl n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butanediol diacetate, 1,6-hexanediol diacetate, triethylene glycol diacetate, γ-butyrolactone, dihexyl malonate, diethyl succinate, dipropyl succinate, dibutyl succinate, dihexyl succinate, dimethyl adipate, diethyl adipate, dibutyl adipate, etc., can be used alone or in combination.
[0186] The boiling point of the aforementioned high-boiling-point solvent can be appropriately selected based on the heat treatment temperature of the material used to form the organic film. Preferably, the boiling point of the added high-boiling-point solvent is 180°C to 300°C, more preferably 200°C to 300°C. With this boiling point, there is no concern that excessively low boiling points will lead to rapid evaporation during baking (heat treatment), thus ensuring sufficient thermal fluidity. Furthermore, with this boiling point, the solvent will not remain in the film after baking due to its high boiling point, thus avoiding any adverse effects on film properties such as etching resistance.
[0187] Furthermore, when using the aforementioned high-boiling-point solvent, the mixing amount of the high-boiling-point solvent is preferably set to 1 to 30 parts by mass relative to 100 parts by mass of the solvent with a boiling point below 180°C. With this mixing amount, there is no need to worry about insufficient mixing amount resulting in inadequate thermal fluidity during baking, or excessive mixing amount resulting in residue in the film and deterioration of film properties such as etching resistance.
[0188] The amount of organic solvent mixed with the above-mentioned compound (A) is preferably 200 to 10,000 parts (by mass; unless otherwise specified, the same applies below) and more preferably 300 to 5,000 parts.
[0189] If it is such an organic film forming material, then by adding a high-boiling-point solvent, the above-mentioned organic film forming compound is given thermal fluidity, thereby becoming an organic film forming material with both high landfill / planarization characteristics.
[0190] <Other Ingredients>
[0191] The organic film forming material of the present invention may further contain one or more of (C) an acid-producing agent, (D) a surfactant, (E) a crosslinking agent and (F) a plasticizer, depending on its purpose.
[0192] (C) Acid-producing agent)
[0193] In the organic film forming material of the present invention, an acid-generating agent may be added as component (C) to further promote the curing reaction. The acid-generating agent may include acid-generating agents that generate acid through thermal decomposition or acid-generating agents that generate acid through light irradiation; both can be added. Specifically, the materials described in paragraphs (0061) to (0085) of Japanese Patent Application Publication No. 2007-199653 may be added, but are not limited to them.
[0194] The aforementioned acid-producing agents can be used alone or in combination of two or more. The amount of acid-producing agent added is preferably 0.05 to 50 parts, more preferably 0.1 to 10 parts, relative to 100 parts of the aforementioned compound.
[0195] ((D) Surfactant)
[0196] In the organic film forming material of the present invention, a surfactant may be added as component (D) to improve the coatability during spin coating. The surfactant may be, for example, the surfactants described in (0142) to (0147) of Japanese Patent Application Publication No. 2009-269953.
[0197] The surfactants described above can be used alone or in combination of two or more. The amount of surfactant added is preferably 0.01 to 10 parts, more preferably 0.05 to 5 parts, relative to 100 parts of the aforementioned compound.
[0198] (E) Crosslinking agent)
[0199] In the organic film-forming material of the present invention, a crosslinking agent may be added as component (E) to improve curability and further suppress mixing with the upper film. There are no particular limitations on the crosslinking agent; various known crosslinking agents can be widely used. Examples include melamine-based crosslinking agents, glycourea-based crosslinking agents, benzoguanamine-based crosslinking agents, urea-based crosslinking agents, β-hydroxyalkylamide-based crosslinking agents, isocyanurate-based crosslinking agents, aziridine-based crosslinking agents, oxazoline-based crosslinking agents, and epoxy-based crosslinking agents.
[0200] As melamine-based crosslinking agents, examples specifically include hexamethoxymethylated melamine, hexabutoxymethylated melamine, their alkoxy and / or hydroxyl substituents, and their partially self-condensing bodies. As glycourea-based crosslinking agents, examples specifically include tetramethoxymethylated glycourea, tetrabutoxymethylated glycourea, their alkoxy and / or hydroxyl substituents, and their partially self-condensing bodies. As benzoguanidine-based crosslinking agents, examples specifically include tetramethoxymethylated benzoguanidine, tetrabutoxymethylated benzoguanidine, their alkoxy and / or hydroxyl substituents, and their partially self-condensing bodies. As urea-based crosslinking agents, examples specifically include dimethoxymethylated dimethoxyvinylurea, its alkoxy and / or hydroxyl substituents, and their partially self-condensing bodies. As β-hydroxyalkylamide-based crosslinking agents, examples specifically include N,N,N',N'-tetra(2-hydroxyethyl)adipamide. Examples of isocyanurate-based crosslinking agents include triglycidyl isocyanurate and triallyl isocyanurate. Examples of aziridine-based crosslinking agents include 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-dihydroxymethylbutanol-tris[3-(1-acrididinyl)propionate]. As oxazoline-based crosslinking agents, examples specifically include 2,2'-isopropylidene bis(4-benzyl-2-oxazoline), 2,2'-isopropylidene bis(4-phenyl-2-oxazoline), 2,2'-methylene bis(4,5-diphenyl-2-oxazoline), 2,2'-methylene bis(4-phenyl-2-oxazoline), 2,2'-methylene bis(4-tert-butyl-2-oxazoline), 2,2'-bis(2-oxazoline), 1,3-phenylidene bis(2-oxazoline), 1,4-phenylidene bis(2-oxazoline), and 2-isopropylidene oxazoline copolymers. Examples of epoxy-based crosslinking agents include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-cyclohexanediethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether.
[0201] As a polynuclear phenolic crosslinking agent, specifically, compounds represented by the following general formula (1E) can be exemplified.
[0202]
[0203] (In the formula, Q is a single bond or an s-valent hydrocarbon group with 1 to 20 carbon atoms. R) 10 It is an alkyl group having 1 to 20 hydrogen atoms or carbon atoms. s is an integer from 1 to 5.
[0204] Q is a single bond or an s-valent hydrocarbon group with 1 to 20 carbon atoms. s is an integer from 1 to 5, more preferably 2 or 3. Specifically, examples of Q include groups obtained by removing s hydrogen atoms from methane, ethane, propane, butane, isobutane, pentane, cyclopentane, hexane, cyclohexane, methylpentane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, benzene, toluene, xylene, ethylbenzene, ethylisopropylbenzene, diisopropylbenzene, methylnaphthalene, ethylnaphthalene, and eicosane. R 10 It is an alkyl group having 1 to 20 carbon atoms or hydrogen atoms. Specifically, examples of alkyl groups having 1 to 20 carbon atoms include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, pentyl, isopentyl, hexyl, octyl, ethylhexyl, decyl, and eicosyl, with hydrogen atoms or methyl atoms being preferred.
[0205] As examples of compounds represented by the above general formula (1E), specifically, the following compounds can be illustrated. Among these, from the viewpoint of improving the curability and thickness uniformity of the organic film, triphenolmethane, triphenolethane, 1,1,1-tris(4-hydroxyphenyl)ethane, and hexamethoxymethylated forms of tris(4-hydroxyphenyl)-1-ethyl-4-isopropylbenzene are preferred. R 10 Same as above.
[0206]
[0207]
[0208] The aforementioned crosslinking agent can be used alone or in combination of two or more. The amount of crosslinking agent added relative to 100 parts of the aforementioned compound is preferably 1 to 100 parts, more preferably 5 to 50 parts.
[0209] (F) Plasticizer
[0210] Furthermore, in order to further improve the planarization / filling properties of the organic film forming material of the present invention, a plasticizer may be added as component (F). There are no particular limitations on the plasticizer, and various known plasticizer systems can be widely used. Examples include low-molecular-weight compounds such as phthalates, adipates, phosphates, trimellitic esters, and citrates, as well as polymers such as polyethers, polyesters, and polyacetal polymers described in Japanese Patent Application Laid-Open No. 2013-253227. The amount of plasticizer added is preferably 1 to 100 parts, more preferably 5 to 30 parts, relative to 100 parts of the aforementioned compound.
[0211] Furthermore, in the organic film-forming material of the present invention, as an additive for imparting landfill / planarization properties in the same way as a plasticizer, a liquid additive having a polyethylene glycol or polypropylene glycol structure, or a thermally degradable polymer with a weight loss rate of 40% by mass or more from 30°C to 250°C and a weight-average molecular weight of 300 to 200,000, is preferably used. This thermally degradable polymer preferably contains repeating units having an acetal structure shown in the following general formulas (DP1) and (DP1a). The amount of these thermally degradable polymers added is preferably 1 to 100 parts, more preferably 5 to 30 parts, relative to 100 parts of the aforementioned compound.
[0212]
[0213] (In the formula, Ra is a hydrogen atom or a monovalent organic group of 1 to 30 saturated or unsaturated carbon atoms that may be substituted. L is a divalent organic group of 2 to 30 saturated or unsaturated carbon atoms.)
[0214]
[0215] (In the formula, Rb is an alkyl group with 1 to 4 carbon atoms. Z is a saturated or unsaturated divalent hydrocarbon group with 4 to 10 carbon atoms, optionally containing an ether bond. t represents the average number of repeating units, which is 3 to 500.)
[0216] Furthermore, as an additive used to improve landfill / leveling characteristics in the same way as described above, a flowability promoter can be used. As a flowability promoter, one or more compounds selected from the following general formulas (i) to (iii) can be used. The amount of these flowability promoters added is preferably 1 to 100 parts, more preferably 5 to 30 parts, relative to 100 parts of the aforementioned compound.
[0217]
[0218] (In the formula, Ra is independently a hydrogen atom, a hydroxyl group, or an organic group with 1 to 10 optionally substituted carbon atoms. W1 is a phenylene group or a divalent group as shown in the following general formula (i-1). W2 and W3 are single bonds or divalent groups as any of the following general formula (i-2). m1 is an integer from 1 to 10, and na is an integer from 0 to 5.)
[0219]
[0220] (In the formula, * indicates the bonding position, Rb, Rc, Rd, and Re are hydrogen atoms, hydroxyl groups, or organic groups with 1 to 10 carbon atoms. W10 and W11 are each independently a single bond or a carbonyl group. m10 and m11 are integers from 0 to 10, and m10 + m11 ≥ 1.)
[0221]
[0222] (In the formula, * indicates the bonding position.)
[0223]
[0224] (In the formula, Rf is independently a hydrogen atom or an organic group with 1 to 10 optional substituted carbon atoms. W4 is a divalent group as shown in the following general formula (ii-1). W5 is a single bond or a divalent group as any of the following general formula (ii-2). m2 is an integer from 2 to 10, and nc is an integer from 0 to 5.)
[0225]
[0226] (In the formula, * indicates the bonding position, Rg, Rh, Ri, and Rj are hydrogen atoms, hydroxyl groups, or organic groups with 1 to 10 carbon atoms. m20 and m21 are integers from 0 to 10, and m20 + m21 ≥ 1.)
[0227]
[0228] (In the formula, Rk and Rl are hydrogen atoms, hydroxyl groups, or organic groups with 1 to 10 optional substituted carbon atoms, optionally bonded to form a cyclic structure. Rm and Rn are organic groups with 1 to 10 carbon atoms, Rm is an aromatic ring or a group containing any of the divalent groups shown in the following general formula (iii-1). W6 and W7 are single bonds or divalent groups as any of the groups shown in the following general formula (iii-2), at least one of which is a divalent group shown in (iii-2).)
[0229]
[0230] (In the formula, * indicates the bonding position, and W30 is an organic group with 1 to 4 carbon atoms.)
[0231]
[0232] (In the formula, * indicates the bonding position.)
[0233] As described above, the organic film-forming material of the present invention is an organic film-forming material that cures without producing byproducts during film formation in an inert gas that prevents substrate corrosion, exhibits good adhesion to the substrate, and combines heat resistance (e.g., above 400°C) with excellent packing / planarization characteristics. Therefore, the organic film-forming material of the present invention is extremely useful as an organic film-forming material for multilayer resist methods such as two-layer resist methods, three-layer resist methods using a silicon-containing resist interlayer or an inorganic hard mask (e.g., a silicon-containing inorganic hard mask), and four-layer resist methods using a silicon-containing resist interlayer or an inorganic hard mask and an organic antireflective film. Furthermore, the organic film-forming material of the present invention does not produce byproducts during film formation in an inert gas and has excellent packing / planarization characteristics; therefore, it can also be suitably used as a planarization material in semiconductor device manufacturing processes other than multilayer resist methods. In other words, the organic film-forming material of the present invention can be suitably used in semiconductor device manufacturing processes.
[0234] <Substrate for Semiconductor Device Manufacturing>
[0235] In addition, the present invention provides a substrate for manufacturing a semiconductor device, characterized in that an organic film formed by curing the organic film forming material of the present invention is formed on the substrate.
[0236] The semiconductor device manufacturing substrate of the present invention may also include a substrate and an organic film formed on the aforementioned substrate, wherein the organic film is a cured product of the organic film forming material of the present invention.
[0237] This semiconductor device manufacturing substrate contains an organic film that combines high heat resistance, good adhesion to the substrate, and high filling / planarization properties. Therefore, if used in the semiconductor device manufacturing process, the yield of semiconductor devices becomes good.
[0238] <Methods for forming organic films>
[0239] The present invention also provides a method for forming an organic film, which uses the organic film forming material of the present invention and is applied in the manufacturing process of a semiconductor device. Specifically, the following methods can be listed.
[0240] (One-stage baking method (in inert gas))
[0241] An organic film forming method is characterized in that it is an organic film forming method used in the manufacturing process of a semiconductor device, wherein the organic film forming material of the present invention is spin-coated onto a substrate to be processed, and the substrate to be processed coated with the organic film forming material is subjected to heat treatment in an inactive gas atmosphere at a temperature of 50°C or higher and 600°C or lower for a range of 5 seconds to 7200 seconds to obtain a cured film.
[0242] (Two-stage baking method (in air - in inert gas))
[0243] An organic film forming method is characterized in that it is an organic film forming method used in the manufacturing process of a semiconductor device, wherein the organic film forming material of the present invention is spin-coated onto a substrate to be processed, and the substrate to be processed coated with the organic film forming material is heat-treated in air at a temperature of 50°C or higher and 300°C for a period of 5 to 600 seconds to form a coated film, and then heat-treated in an inert gas atmosphere at a temperature of 200°C or higher and 600°C for a period of 10 to 7200 seconds to obtain a cured film.
[0244] In the method for forming the organic film of the present invention, firstly, the organic film forming material of the present invention is spin-coated onto the substrate to be processed.
[0245] In the organic film formation method of the present invention, the substrate coated with the organic film forming material is then subjected to heat treatment (heating film formation process) to obtain a cured film.
[0246] The heating film-forming process used to form a cured film can employ one-stage baking, two-stage baking, or multi-stage baking with three or more stages. One-stage baking or two-stage baking is preferred from an economic perspective.
[0247] Film formation based on a one-stage baking process is preferably performed at a temperature of 50°C or higher and 600°C or lower for 5 to 7200 seconds, more preferably at a temperature of 150°C or higher and 500°C or lower for 10 to 7200 seconds (more preferably 10 to 3600 seconds). By utilizing these conditions for heat treatment, planarization and crosslinking reactions based on heat flow can be promoted. In multilayer resist methods, a coated silicon-containing resist interlayer film and a CVD hard mask are sometimes formed on the resulting film. When using a coated silicon-containing resist interlayer film, film formation is preferably performed at a temperature higher than the temperature at which the silicon-containing resist interlayer film is formed. Typically, the silicon-containing resist interlayer film is formed at 100°C or higher and 400°C or lower, preferably at 150°C or higher and 350°C or lower. If the organic film is formed at a temperature higher than this, the dissolution of the organic film caused by the silicon-containing resist interlayer film material can be prevented, forming an organic film that does not mix with the material.
[0248] When using a CVD hard mask, it is preferable to form the organic film at a temperature higher than the temperature at which the CVD hard mask is formed. Examples of temperatures for forming a CVD hard mask include temperatures of 150°C or higher and 500°C or lower.
[0249] Furthermore, inert gases such as nitrogen, argon, and helium can be used as the atmosphere for baking. With the material of the present invention, an organic film can be formed that fully solidifies without producing sublimation even when calcined in such an inert gas atmosphere. Moreover, with the material of the present invention, it can solidify without producing byproducts even during film formation in an inert gas that prevents substrate corrosion.
[0250] That is, one aspect of the organic film formation method of the present invention is an organic film formation method, characterized in that it is an organic film formation method used in the manufacturing process of a semiconductor device, wherein the organic film forming material of the present invention is spin-coated onto a substrate to be processed, and the substrate to be processed coated with the organic film forming material is heat-treated in an inactive gas atmosphere at a temperature of 50°C or higher and 600°C or lower for a period of 5 seconds to 7200 seconds to obtain a cured film.
[0251] On the other hand, in film formation based on two-stage baking, for example, a first-stage baking process can be performed in which the substrate coated with the organic film forming material of the present invention is heat-treated in air, followed by a second-stage baking process in an inactive gas atmosphere.
[0252] Regarding the first stage of baking, considering the effect of substrate corrosion caused by oxygen in the air, it is performed within a range of 5 to 600 seconds, with an upper limit of the air processing temperature of 300°C or less, preferably 250°C or less. The lower limit of the air processing temperature can be set, for example, to 50°C.
[0253] Examples of inert gases used in the second stage of baking include nitrogen, argon, and helium. With the material of the present invention, an organic film can be formed that fully solidifies without producing sublimation even when calcined in such an inert gas atmosphere. Furthermore, with the material of the present invention, film formation can be achieved even in an inert gas atmosphere designed to prevent substrate corrosion, without producing byproducts.
[0254] The baking temperature for the second stage is preferably higher than that of the first stage, for example, set to a temperature of 200°C or higher and 600°C or lower, preferably 500°C or lower, and performed for 10 to 7200 seconds. In the multilayer resist method, a coated silicon-containing resist intermediate film and a CVD hard mask are sometimes formed on the resulting film. When using a coated silicon-containing resist intermediate film, film formation at a temperature higher than the temperature at which the silicon-containing resist intermediate film is formed is preferred. Typically, the silicon-containing resist intermediate film is formed at 100°C or higher and 400°C or lower, preferably 150°C or higher and 350°C or lower. If an organic film is formed at a temperature higher than this, the dissolution of the organic film caused by the silicon-containing resist intermediate film material can be prevented, forming an organic film that does not mix with the material.
[0255] When using a CVD hard mask in a two-stage baking process, it is preferable to form the organic film at a temperature higher than the temperature at which the CVD hard mask is formed. Examples of temperatures for forming the CVD hard mask include temperatures of 150°C or higher and 500°C or lower.
[0256] That is, one aspect of the organic film formation method of the present invention is an organic film formation method characterized in that it is an organic film formation method used in the manufacturing process of a semiconductor device, wherein the organic film forming material of the present invention is spin-coated onto a substrate to be processed, and the substrate to be processed coated with the organic film forming material is heat-treated in air at a temperature of 50°C or higher and 300°C or lower for a period of 5 to 600 seconds to form a coated film, and then heat-treated in an inert gas atmosphere at a temperature of 200°C or higher and 600°C or lower for a period of 10 to 7200 seconds to obtain a cured film.
[0257] Preferably, the oxygen concentration in the aforementioned inactive gas is set to less than 1% by volume.
[0258] If the organic film forming material of the present invention is used, it is possible to form an organic film that fully cures without producing sublimation even when heated (heat-treated) in such an inert gas atmosphere, and also exhibits excellent adhesion to the substrate. Furthermore, by heating in such an inert gas atmosphere, corrosion of the processed substrate can be prevented.
[0259] That is, in this invention, a method for forming an organic film is provided, which is an organic film that functions as an organic film used in the manufacturing process of a semiconductor device. In order to prevent corrosion of the substrate being processed, the aforementioned heat treatment in an inactive gas atmosphere is performed by heat treating the substrate being processed in an atmosphere with an oxygen concentration of less than 1% by volume to form a cured film.
[0260] In this method of forming the organic film, firstly, the organic film forming material of the present invention is spin-coated onto a substrate to be processed. After spin-coating, in a two-stage baking process, firstly, baking is performed in air at a temperature below 300°C, followed by a second-stage baking in an atmosphere with an oxygen concentration of 1% by volume or less. In the case of a one-stage baking process, the initial baking in air can be omitted. It should be noted that inert gases such as nitrogen, argon, and helium can be used as examples of the baking atmosphere. With the material of the present invention, an organic film can be formed that is fully cured without producing sublimation even when calcined in such an inert gas atmosphere.
[0261] Furthermore, in the method for forming the organic film of the present invention, a substrate having a structure or elevation difference with a height of 30 nm or more can be used. As described above, the material for forming the organic film of the present invention has excellent packing / planarization characteristics; therefore, even if the substrate has a structure or elevation difference (unevenness) with a height of 30 nm or more, a flat cured film can be formed. In other words, the method for forming the organic film of the present invention is particularly useful when forming a flat organic film on such a substrate.
[0262] It should be noted that the thickness of the formed organic film can be appropriately selected, preferably 30 to 20,000 nm, and particularly preferably 50 to 15,000 nm.
[0263] Furthermore, the above-described method for forming organic films can be applied to both the case of forming an organic film using the organic film forming material of the present invention and the case of forming an organic film for planarization.
[0264] For example, a variation of the organic film formation method of the present invention is an organic film formation method that can planarize the surface of a substrate with uneven surfaces used in a semiconductor device manufacturing process. In this method, the organic film forming material of the present invention is spin-coated onto a substrate to be processed. The substrate to be processed coated with the organic film forming material is then heat-treated in air at a temperature of 50°C or higher and 300°C or lower for 5 to 600 seconds. Next, it is heat-treated in an inert gas atmosphere at a temperature of 200°C or higher and 600°C or lower for 10 to 7200 seconds, thereby forming a cured film.
[0265] In this method of forming the organic film, firstly, the organic film forming material of the present invention is spin-coated onto a substrate. By using spin-coating, good embedding properties can be obtained. After spin-coating, baking (heat treatment) is performed to promote planarization and crosslinking reactions based on thermal flow. It should be noted that this baking allows the solvent in the material to evaporate, thus preventing mixing when a resist upper layer and a silicon-containing resist intermediate layer are formed on the organic film.
[0266] <Pattern Formation Methods>
[0267] The organic film forming material of the present invention is applicable to various patterning methods, such as three-layer resist processes using silicon-containing resist interlayers or inorganic hard masks, and four-layer resist processes using organic anti-reflective films. In the manufacturing process of semiconductor devices, if circuit patterns are formed using this patterning method of the present invention, semiconductor devices can be manufactured with good yield. Examples of patterning methods using the organic film forming material of the present invention are given below.
[0268] (1) A pattern forming method, characterized in that an organic film is formed on a workpiece using an organic film forming material of the present invention, a silicon-containing photoresist intermediate film is formed on the organic film using a silicon-containing photoresist intermediate film material, a photoresist upper film is formed on the silicon-containing photoresist intermediate film using a photoresist composition, a circuit pattern is formed on the photoresist upper film, a pattern is transferred to the aforementioned silicon-containing photoresist intermediate film by etching using the photoresist upper film with the pattern formed thereon as a mask, a pattern is transferred to the aforementioned organic film by etching using the photoresist intermediate film with the pattern transferred thereon as a mask, and then a pattern is transferred to the aforementioned workpiece by etching using the organic film with the pattern transferred thereon as a mask.
[0269] (2) A pattern forming method, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention, a silicon-containing photoresist intermediate film is formed on the organic film using a silicon-containing photoresist intermediate film material, an organic anti-reflective film is formed on the silicon-containing photoresist intermediate film, a photoresist upper film is formed on the organic anti-reflective film using a photoresist composition to form a four-layer film structure, a circuit pattern is formed on the photoresist upper film, the photoresist upper film with the pattern is used as a mask, the pattern is transferred to the aforementioned organic anti-reflective film and the aforementioned silicon-containing photoresist intermediate film by etching, the pattern is transferred to the aforementioned organic film by etching using the silicon-containing photoresist intermediate film with the transferred pattern as a mask, and then the pattern is transferred to the aforementioned workpiece by etching using the organic film with the transferred pattern as a mask.
[0270] (3) A pattern forming method, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention, an inorganic hard mask selected from silicon oxide film, silicon nitride film, silicon nitride film, titanium oxide film, and titanium nitride film is formed on the organic film, a photoresist upper layer film is formed on the inorganic hard mask using a photoresist composition, a circuit pattern is formed on the photoresist upper layer film, the photoresist upper layer film with the pattern is used as a mask, the pattern is transferred to the aforementioned inorganic hard mask by etching, the pattern is transferred to the aforementioned organic film by etching using the inorganic hard mask with the transferred pattern as a mask, and then the pattern is transferred to the aforementioned workpiece by etching using the organic film with the transferred pattern as a mask.
[0271] (4) A pattern forming method, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention, an inorganic hard mask selected from silicon oxide film, silicon nitride film, silicon nitride film, titanium oxide film, and titanium nitride film is formed on the organic film, an organic antireflective film is formed on the inorganic hard mask, a photoresist upper film is formed on the organic antireflective film using a photoresist composition to form a four-layer film structure, a circuit pattern is formed on the photoresist upper film, the photoresist upper film with the pattern is used as a mask, the pattern is transferred to the aforementioned organic antireflective film and the aforementioned inorganic hard mask by etching, the pattern is transferred to the aforementioned organic film by etching using the inorganic hard mask with the transferred pattern as a mask, and then the pattern is transferred to the aforementioned workpiece by etching using the organic film with the transferred pattern as a mask.
[0272] The following examples illustrate methods for forming patterns, but are not limited to these.
[0273] [Three-layer photoresist method using a silicon-containing photoresist interlayer]
[0274] Furthermore, this invention provides a pattern forming method, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention described above; a silicon-containing photoresist intermediate film is formed on the organic film using a silicon-containing photoresist intermediate film material; a photoresist upper film is formed on the silicon-containing photoresist intermediate film using a photoresist composition; a circuit pattern is formed on the photoresist upper film; the silicon-containing photoresist intermediate film with the pattern formed is used as a mask to etch the aforementioned silicon-containing photoresist intermediate film; the pattern is transferred to the silicon-containing photoresist intermediate film; the organic film is etched using the silicon-containing photoresist intermediate film with the transferred pattern as a mask; the pattern is transferred to the organic film; and then, the workpiece is etched using the organic film with the transferred pattern as a mask; the pattern is transferred to the workpiece.
[0275] As the workpiece, it is preferable to use a semiconductor device substrate or a workpiece on which a metal film, metal carbide film, metal oxide film, metal nitride film, metal oxide carbide film, and metal oxynitride film are formed. More specifically, there is no particular limitation, and substrates such as Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, and Al can be used; workpieces on which the above-mentioned metal films are formed as the workpiece layer can be used.
[0276] As the processed layer, various Low-k films and their barrier films, such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, and Al-Si, can be used, typically forming thicknesses of 50–10,000 nm, especially 100–5,000 nm. It should be noted that when forming the processed layer, the substrate and the processed layer can be made of different materials.
[0277] It should be noted that the metal constituting the workpiece preferably includes silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or alloys thereof.
[0278] In addition, as the workpiece, a structure with a height of 30 nm or more or a substrate with a height difference can be used.
[0279] When forming an organic film on a workpiece using the organic film forming material of the present invention, the organic film forming method of the present invention described above can be applied.
[0280] Next, a photoresist interlayer (silicon-containing photoresist interlayer) is formed on the organic film using a photoresist interlayer material containing silicon atoms. A polysiloxane-based interlayer material is preferred as the silicon-containing photoresist interlayer material. By giving the silicon-containing photoresist interlayer an anti-reflective effect, reflection can be suppressed. In particular, for 193nm exposure applications, if a material containing a large number of aromatic groups and with high etching selectivity to the substrate is used as the organic film forming material, the k-value becomes high, and the substrate reflection becomes high. By giving the silicon-containing photoresist interlayer an absorption value that exhibits an appropriate k-value, reflection can be suppressed, and the substrate reflection can be set to 0.5% or less. For 248nm and 157nm exposure applications, anthracene is preferred as the silicon-containing photoresist interlayer with anti-reflective effect. For 193nm exposure applications, a polysiloxane having phenyl groups or light-absorbing groups with silicon-silicon bonds in its side group structure or polysiloxane structure and crosslinked by acid or heat is preferred.
[0281] Next, a photoresist top layer film is formed on the silicon-containing photoresist intermediate film using a photoresist top layer film material comprising a photoresist composition. The photoresist top layer film material can be either positive or negative, and can be the same material as commonly used photoresist compositions. Preferably, after spin-coating the photoresist top layer film material, pre-baking is performed within the range of 60–180°C for 10–300 seconds. Subsequently, exposure is performed according to conventional methods, followed by post-exposure baking (PEB) and development to obtain the photoresist top layer film pattern. It should be noted that the thickness of the photoresist top layer film is not particularly limited, but is preferably 30–500 nm, and particularly preferably 50–400 nm.
[0282] Next, a circuit pattern (resist top film pattern) is formed on the resist top film. In forming the circuit pattern, it is preferable to form the circuit pattern by photolithography using light with a wavelength of 10 nm or more and 300 nm or less, direct electron beam drawing, nanoimprinting, or a combination thereof.
[0283] It should be noted that, as exposure light, high-energy rays with wavelengths below 300nm can be listed, specifically far-ultraviolet light, KrF excimer laser (248nm), ArF excimer laser (193nm), F2 laser (157nm), Kr2 laser (146nm), Ar2 laser (126nm), soft X-rays (EUV) of 3-20nm, electron beam (EB), ion beam, X-rays, etc.
[0284] In addition, during the formation of the circuit pattern, it is preferable to use an alkali or organic solvent to develop the circuit pattern.
[0285] Next, using the resist upper layer film with the circuit pattern as a mask, the silicon-containing resist intermediate film is etched to transfer the pattern onto the silicon-containing resist intermediate film. The etching of the silicon-containing resist intermediate film using the resist upper layer film pattern as a mask is preferably performed using a fluorocarbon-based gas. This forms the silicon-containing resist intermediate film pattern.
[0286] Next, the organic film is etched using a patterned silicon resist interlayer as a mask, thus transferring the pattern onto the organic film. Compared to the organic film, the silicon resist interlayer exhibits higher etch resistance to oxygen or hydrogen; therefore, the etching of the organic film using the patterned silicon resist interlayer as a mask is preferably performed using an etching gas primarily composed of oxygen or hydrogen. This allows the formation of an organic film pattern.
[0287] Next, the workpiece is etched using a patterned organic film as a mask, transferring the pattern onto the workpiece. The etching of the workpiece (processed layer) can be performed using conventional methods. For example, if the workpiece is a SiO2, SiN, or silicon dioxide-based low-dielectric-constant insulating film, etching with a Freon-based gas is performed; if it is p-Si, Al, or W, etching with a chlorine-based or bromine-based gas is performed. When substrate processing is performed using Freon-based gas etching, the silicon resist interlayer pattern is stripped away simultaneously with substrate processing. On the other hand, when substrate processing is performed using chlorine-based or bromine-based gas etching, dry etching with a Freon-based gas is required after substrate processing to strip the silicon resist interlayer pattern.
[0288] Organic films obtained using the organic film forming material of the present invention enable the processed body described above to exhibit excellent etch resistance during etching.
[0289] [Four-layer resist method using a silicon-containing resist interlayer and an organic anti-reflective film]
[0290] Furthermore, this invention provides a pattern forming method, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention described above; a silicon-containing photoresist intermediate film is formed on the organic film using a silicon-containing photoresist intermediate film material; an organic antireflective film is formed on the silicon-containing photoresist intermediate film; a photoresist upper film is formed on the organic antireflective film using a photoresist composition to form a photoresist upper film, thereby forming a four-layer film structure; a circuit pattern is formed on the photoresist upper film; the photoresist upper film with the pattern formed is used as a mask to etch the aforementioned organic antireflective film and the aforementioned silicon-containing photoresist intermediate film; a pattern is transferred onto the organic antireflective film and the silicon-containing photoresist intermediate film; the silicon-containing photoresist intermediate film with the transferred pattern is used as a mask to etch the aforementioned organic film; a pattern is transferred onto the aforementioned organic film; and further, the workpiece is etched using the organic film with the transferred pattern as a mask; a pattern is transferred onto the workpiece.
[0291] It should be noted that, apart from forming an organic antireflective film (BARC) between the silicon-containing photoresist intermediate film and the photoresist top film, this method can be performed in the same manner as the three-layer photoresist method using a silicon-containing photoresist intermediate film described above.
[0292] Organic antireflective films can be formed using known organic antireflective film materials through spin coating.
[0293] [Three-layer resist method using inorganic hard mask]
[0294] Furthermore, in this invention, as a pattern forming method based on a three-layer resist method using the organic film forming material of the present invention, a pattern forming method is provided, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention, an inorganic hard mask selected from silicon oxide film, silicon nitride film, silicon nitride film, titanium oxide film, and titanium nitride film is formed on the organic film, a photoresist upper layer film is formed on the inorganic hard mask using a photoresist composition, a circuit pattern is formed on the photoresist upper layer film, the photoresist upper layer film with the pattern formed is used as a mask, the aforementioned inorganic hard mask is etched, and a pattern is transferred to the inorganic hard mask, the aforementioned organic film is etched using the inorganic hard mask with the transferred pattern as a mask, and a pattern is transferred to the organic film, and then the aforementioned workpiece is etched using the organic film with the transferred pattern as a mask, and a pattern is transferred to the workpiece.
[0295] It should be noted that, apart from forming an inorganic hard mask on the organic film to replace the silicon-containing photoresist intermediate film, this method is performed in the same manner as the three-layer photoresist method using the silicon-containing photoresist intermediate film described above.
[0296] Inorganic hard masks selected from silicon oxide films, silicon nitride films, and silicon nitride oxide films (SiON films) can be formed using CVD methods, ALD methods, etc. Methods for forming silicon nitride films are described, for example, in Japanese Patent Application Publication No. 2002-334869 and International Publication No. 2004 / 066377. The thickness of the inorganic hard mask is preferably 5 to 200 nm, more preferably 10 to 100 nm. As the inorganic hard mask, SiON films, which are highly effective as anti-reflective films, are most preferably used. Since the substrate temperature reaches 300 to 500°C when forming the SiON film, the organic film needs to be able to withstand temperatures of 300 to 500°C. The organic film formed using the organic film forming material of the present invention has high heat resistance and can withstand high temperatures of 300 to 500°C; therefore, it can be a combination of an inorganic hard mask formed by CVD or ALD methods and an organic film formed by spin coating.
[0297] Inorganic hard masks selected from titanium oxide and titanium nitride films are also formed by CVD, ALD and other methods.
[0298] [A four-layer photoresist method using an inorganic hard mask and an organic anti-reflective film]
[0299] Furthermore, in this invention, as a pattern forming method based on the four-layer resist method using the organic film forming material of the present invention, a pattern forming method is provided, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention, an inorganic hard mask selected from silicon oxide film, silicon nitride film, silicon nitride film, titanium oxide film, and titanium nitride film is formed on the organic film, an organic antireflective film is formed on the inorganic hard mask, a resist upper layer film is formed on the organic antireflective film using a photoresist composition to form a four-layer film structure, a circuit pattern is formed on the resist upper layer film, the aforementioned organic antireflective film and the aforementioned inorganic hard mask are etched using the resist upper layer film with the pattern formed as a mask, the pattern is transferred to the organic antireflective film and the inorganic hard mask, the aforementioned organic film is etched using the inorganic hard mask with the transferred pattern as a mask, the pattern is transferred to the organic film, and then the aforementioned workpiece is etched using the organic film with the transferred pattern as a mask, and the pattern is transferred to the workpiece.
[0300] It should be noted that, apart from forming an organic antireflective film (BARC) between the inorganic hard mask and the upper layer of the resist, this method can be performed in the same manner as the three-layer resist method using an inorganic hard mask described above.
[0301] Especially when using SiON film as an inorganic hard mask, reflection can be suppressed even in immersion exposure with high photoresistivity (NA) exceeding 1.0 through the two layers of antireflective film, SiON film and BARC. Another advantage of forming BARC is that it reduces the curling of the resist pattern directly above the SiON film.
[0302] Here, an example of the pattern formation method based on the three-layer resist method of the present invention is shown. Figure 2 (A) to (F). In the case of the three-layer resist method, such as Figure 2 As shown in (A), using the organic film forming material of the present invention, after forming an organic film 3 on the processed layer 2 formed on the substrate 1, a silicon-containing photoresist intermediate film 4 is formed, and a photoresist upper layer film 5 is formed thereon. Next, as... Figure 2 As shown in (B), the exposed portion 6 of the resist upper film 5 is exposed to PEB (post-exposure baking). Next, as... Figure 2 As shown in (C), development is performed to form the resist upper film pattern 5a. Then, as... Figure 2 As shown in (D), using the upper resist film pattern 5a as a mask, a Freon-based gas is used to dry-etch the silicon-containing resist intermediate film 4 to form the silicon-containing resist intermediate film pattern 4a. Then, as... Figure 2As shown in (E), after removing the upper resist film pattern 5a, the organic film 3 is subjected to oxygen plasma etching using the silicon-containing resist intermediate film pattern 4a as a mask to form the organic film pattern 3a. Furthermore, as... Figure 2 As shown in (F), after removing the silicon resist intermediate film pattern 4a, the organic film pattern 3a is used as a mask to etch the processed layer 2 to form pattern 2a.
[0303] When forming an inorganic hard mask, it is sufficient to simply replace the silicon-containing photoresist intermediate film 4 with an inorganic hard mask. When forming a BARC, it is sufficient to form a BARC between the silicon-containing photoresist intermediate film 4 and the upper photoresist film 5. The etching of the BARC can be performed continuously before the etching of the silicon-containing photoresist intermediate film 4, or the etching equipment can be changed to etch the silicon-containing photoresist intermediate film 4 after only the etching of the BARC is performed.
[0304] As described above, if it is the pattern forming method of the present invention, then a fine pattern can be formed on the workpiece with high precision by means of a multilayer resist method.
[0305] Example
[0306] The following examples, comparative examples, embodiments, and comparative examples illustrate the present invention in more detail, but the present invention is not limited thereto. It should be noted that the molecular weight and dispersity were determined by gel permeation chromatography (GPC) using tetrahydrofuran as the eluent, yielding the weight-average molecular weight (Mw) and number-average molecular weight (Mn) of polystyrene, and the dispersity (Mw / Mn).
[0307] Synthesis of compounds for organic film formation
[0308] In the synthesis of organic film forming compounds (A1) to (A13), fluorene alcohols (B1) to (B7), phenols and naphthols (C1) to (C4) are used.
[0309] Fluorene alcohols:
[0310]
[0311] Phenol or naphthol:
[0312]
[0313] As an example of the synthesis of fluorene alcohols, the synthesis example of (B1) is shown below. [Synthesis Example 1] Synthesis of fluorene alcohol (B1)
[0314]
[0315] 500 mL of 2.60 M hexane solution of n-butyllithium was added to a mixture of 189.9 g of tris(4-bromophenyl)amine (D1), 1000 mL of MTBE (tert-butyl methyl ether), and 1000 mL of THF (tetrahydrofuran) cooled to -20 °C under N2 atmosphere, and the mixture was stirred at -20 °C for 20 minutes. A 25 wt% THF solution prepared by dissolving 191.7 g of 9-fluorenone in THF was slowly added dropwise, and the mixture was slowly heated to room temperature and stirred at room temperature for 4 hours. After stopping the reaction by adding 1000 mL of saturated ammonium chloride aqueous solution, 2000 mL of MTBE was added, and the separated aqueous layer was removed. The organic layer was then washed five times with 500 mL of pure water, and the solvent was removed by distillation. After distillation, 500 g of THF was added, followed by 2000 g of methanol for recrystallization. The precipitated crystals were separated by filtration, washed twice with 500 g of methanol, and recovered. Compound (B1) was obtained by vacuum drying the recovered crystals at 70°C.
[0316] For the other fluorene alcohols (B2) to (B7), the fluorene alcohol sources shown below were used for synthesis. Specifically, the compounds corresponding to the starting material (D1) used in Synthesis Example 1 were replaced with the corresponding bromides (D2) to (D7) according to the structure of the target compound. The molar ratios of the n-butyllithium solution and 9-fluorene ketone were set as in Synthesis Example 1, and (B2) to (B7) were synthesized respectively. It should be noted that for (B5), the ketone of (D8) was used instead of 9-fluorene ketone for synthesis.
[0317] Fluorene alcohol raw materials:
[0318]
[0319] [Synthesis Example 2] Synthesis of compound (A1)
[0320]
[0321] Compound (B1) 30.0 g, compound (C1) 55.0 g, and 1,2-dichloroethane 400 g were added under a nitrogen atmosphere and a homogeneous dispersion was prepared at an internal temperature of 60 °C. Methanesulfonic acid 22.0 g was slowly added, and the reaction was carried out at an internal temperature of 70 °C for 1 hour. After the reaction was completed, the mixture was cooled to room temperature, and 1000 ml of MIBK (methyl isobutyl ketone) was added. The mixture was washed six times with 200 ml of pure water, and the organic layer was dried under reduced pressure. A homogeneous solution was prepared by adding 200 g of THF to the residue, and crystals were precipitated in 2000 g of IPE (diisopropyl ether). The precipitated crystals were separated by filtration, washed twice with 500 g of IPE, and recovered. Compound (A1) was obtained by vacuum drying the recovered crystals at 70 °C.
[0322] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0323] (A1): Mw=1350, Mw / Mn=1.04
[0324] [Synthesis Example 3] Synthesis of compound (A2)
[0325]
[0326] Compound (B2) 30.0 g, compound (C1) 19.9 g, and 1,2-dichloroethane 250 g were added under a nitrogen atmosphere and a homogeneous dispersion was prepared at an internal temperature of 60 °C. Methanesulfonic acid 20.4 g was slowly added, and the reaction was carried out at an internal temperature of 70 °C for 3 hours. After the reaction was completed, the mixture was cooled to room temperature, 1000 ml of MIBK was added, and the mixture was washed six times with 200 ml of pure water. The organic layer was then dried under reduced pressure. A homogeneous solution was prepared by adding 100 g of THF to the residue, and crystallization was carried out in 1000 g of IPE (diisopropyl ether). The precipitated crystals were separated by filtration, washed twice with 300 g of IPE, and recovered. Compound (A2) was obtained by vacuum drying the recovered crystals at 70 °C.
[0327] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0328] (A2): Mw=1520, Mw / Mn=1.04
[0329] [Synthesis Example 4] Synthesis of compound (A3)
[0330]
[0331] Compound (A1) 10.0 g, potassium carbonate 10.3 g, and DMF (N,N-dimethylformamide) 60 g were added under a nitrogen atmosphere and a homogeneous dispersion was prepared at an internal temperature of 50 °C. Proprynne bromide 8.8 g was slowly added, and the reaction was carried out at an internal temperature of 50 °C for 16 hours. After the reaction was complete, 150 ml of MIBK was added, and the mixture was washed six times with 50 ml of pure water. The organic layer was then dried under reduced pressure. A homogeneous solution was prepared by adding 40 g of MIBK to the residue, and crystallization was carried out in 200 g of MeOH (methanol). The precipitated crystals were separated by filtration, washed twice with 100 g of MeOH, and recovered. Compound (A3) was obtained by vacuum drying the recovered crystals at 70 °C.
[0332] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0333] (A3): Mw=1590, Mw / Mn=1.04
[0334] [Synthesis Example 5] Synthesis of compound (A4)
[0335]
[0336] Compound (A2) 10.0 g, potassium carbonate 9.8 g, and DMF 60 g were added under a nitrogen atmosphere and a homogeneous dispersion was prepared at an internal temperature of 50 °C. Proprynne bromide 8.4 g was slowly added, and the reaction was carried out at an internal temperature of 50 °C for 16 hours. After the reaction was complete, 150 ml of MIBK was added, and the mixture was washed six times with 50 ml of pure water. The organic layer was then dried under reduced pressure. A homogeneous solution was prepared by adding 40 g of MIBK to the residue, and crystallization was carried out in 200 g of MeOH. The precipitated crystals were separated by filtration, washed twice with 100 g of MeOH, and recovered. Compound (A4) was obtained by vacuum drying the recovered crystals at 70 °C.
[0337] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0338] (A4): Mw=1830, Mw / Mn=1.04
[0339] [Synthesis Example 6] Synthesis of compound (A5)
[0340]
[0341] Under a nitrogen atmosphere, 20.0 g of compound (B3), 21.5 g of compound (C1), and 200 g of 1,2-dichloroethane were added, and a homogeneous dispersion was prepared at an internal temperature of 60°C. 12.9 g of methanesulfonic acid was slowly added, and the reaction was carried out at an internal temperature of 70°C for 3 hours. After the reaction was complete, the mixture was cooled to room temperature, 1000 ml of MIBK was added, and the mixture was washed six times with 200 ml of pure water to solidify the organic layer under reduced pressure. 100 g of THF was added to the residue to prepare a homogeneous solution, and 300 g of hexane was added dropwise while stirring, causing a cake-like precipitate to form. After standing for a while, the clear supernatant was decanted. Another 100 g of THF was added to prepare a homogeneous solution, and 300 g of hexane was added to precipitate a cake-like precipitate. After standing, the supernatant was decanted. After adding DMF to the precipitate to form a homogeneous solution, the precipitate was removed by vacuum distillation and DMF was added again, and the solution was adjusted to 30 wt% DMF based on the yield.
[0342] 23.9 g of potassium carbonate was added to the obtained DMF solution, and a homogeneous dispersion was prepared under a nitrogen atmosphere and an internal temperature of 50 °C. 20.6 g of propargyl bromide was slowly added, and the reaction was carried out for 16 hours at an internal temperature of 50 °C. After the reaction was complete, 300 ml of MIBK was added, and the mixture was washed six times with 100 ml of pure water. The organic layer was then dried under reduced pressure. 80 g of MIBK was added to the residue to prepare a homogeneous solution, which was then crystallized in 400 g of MeOH. The precipitated crystals were separated by filtration, washed twice with 200 g of MeOH, and recovered. Compound (A5) was obtained by vacuum drying the recovered crystals at 70 °C.
[0343] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0344] (A5): Mw=1750, Mw / Mn=1.05
[0345] [Synthesis Example 7] Synthesis of Compound (A6)
[0346]
[0347] Under a nitrogen atmosphere, 20.0 g of compound (B4), 17.5 g of compound (C1), and 190 g of 1,2-dichloroethane were added to prepare a homogeneous solution at an internal temperature of 60°C. 10.5 g of methanesulfonic acid was slowly added, and the reaction was carried out at an internal temperature of 70°C for 3 hours. After the reaction was complete, the mixture was cooled to room temperature, 1000 ml of MIBK was added, and the mixture was washed six times with 200 ml of pure water to solidify the organic layer under reduced pressure. 100 g of THF was added to the residue to prepare a homogeneous solution, and 300 g of hexane was added dropwise while stirring to precipitate a rice cake-like precipitate. After standing for a while, the clear supernatant was decanted. 100 g of THF was added again to prepare a homogeneous solution, and 300 g of hexane was added to precipitate another rice cake-like precipitate. After standing, the supernatant was decanted. After adding DMF to the precipitate to form a homogeneous solution, the precipitate was removed by vacuum distillation and DMF was added again, and the solution was adjusted to 30 wt% DMF based on the yield.
[0348] Potassium carbonate (22.6 g) was added to the resulting DMF solution, and a homogeneous dispersion was prepared under a nitrogen atmosphere and an internal temperature of 50 °C. Propylbromine (19.5 g) was slowly added, and the reaction was carried out at 50 °C for 16 hours. After the reaction was complete, MIBK (300 ml) was added, and the mixture was washed six times with 100 ml of pure water. The organic layer was then dried under reduced pressure. MIBK (80 g) was added to the residue to prepare a homogeneous solution, which was then crystallized in MeOH (400 g). The precipitated crystals were separated by filtration, washed twice with MeOH (200 g), and recovered. Compound (A6) was obtained by vacuum drying the recovered crystals at 70 °C.
[0349] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0350] (A6): Mw=1870, Mw / Mn=1.03
[0351] [Synthesis Example 8] Synthesis of Compound (A7)
[0352]
[0353] Under a nitrogen atmosphere, 20.0 g of compound (B5), 12.8 g of compound (C1), and 160 g of 1,2-dichloroethane were added to prepare a homogeneous solution at an internal temperature of 60°C. 7.7 g of methanesulfonic acid was slowly added, and the reaction was carried out at an internal temperature of 70°C for 3 hours. After the reaction was complete, the mixture was cooled to room temperature, 1000 ml of MIBK was added, and the mixture was washed six times with 200 ml of pure water to solidify the organic layer under reduced pressure. 100 g of THF was added to the residue to prepare a homogeneous solution, and 300 g of hexane was added dropwise while stirring, causing a rice cake-like precipitate to form. After standing for a short time, the clear supernatant was decanted. Another 100 g of THF was added to prepare a homogeneous solution, and 300 g of hexane was added to precipitate the rice cake-like precipitate. After standing, the supernatant was decanted. After adding DMF to the precipitate to form a homogeneous solution, the precipitate was removed by vacuum distillation and DMF was added again, and the solution was adjusted to 30 wt% DMF based on the yield.
[0354] 16.6 g of potassium carbonate was added to the obtained DMF solution, and a homogeneous dispersion was prepared under a nitrogen atmosphere and an internal temperature of 50 °C. 14.3 g of propargyl bromide was slowly added, and the reaction was carried out for 16 hours at an internal temperature of 50 °C. After the reaction was complete, 300 ml of MIBK was added, and the mixture was washed six times with 100 ml of pure water. The organic layer was then dried under reduced pressure. 80 g of MIBK was added to the residue to prepare a homogeneous solution, which was then crystallized in 400 g of MeOH. The precipitated crystals were separated by filtration, washed twice with 200 g of MeOH, and recovered. Compound (A7) was obtained by vacuum drying the recovered crystals at 70 °C.
[0355] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0356] (A7): Mw=2320, Mw / Mn=1.05
[0357] [Synthesis Example 9] Synthesis of compound (A8)
[0358]
[0359] Under a nitrogen atmosphere, 20.0 g of compound (B6), 18.5 g of compound (C1), and 200 g of 1,2-dichloroethane were added, and a homogeneous dispersion was prepared at an internal temperature of 60°C. 11.1 g of methanesulfonic acid was slowly added, and the reaction was carried out at an internal temperature of 70°C for 3 hours. After the reaction was complete, the mixture was cooled to room temperature, 1000 ml of MIBK was added, and the mixture was washed six times with 200 ml of pure water. The organic layer was then dried under reduced pressure. 100 g of THF was added to the residue to prepare a homogeneous solution, and 300 g of hexane was added dropwise while stirring, causing a rice cake-like precipitate to form. After standing for a short time, the clear supernatant was decanted. Another 100 g of THF was added to prepare a homogeneous solution, and 300 g of hexane was added to precipitate the rice cake-like precipitate. After standing, the supernatant was decanted. After adding DMF to the precipitate to form a homogeneous solution, the precipitate was removed by vacuum distillation and DMF was added again, and the solution was adjusted to 30 wt% DMF based on the yield.
[0360] Potassium carbonate (26.5 g) was added to the resulting DMF solution, and a homogeneous dispersion was prepared under a nitrogen atmosphere and an internal temperature of 50 °C. Allyl bromide (23.2 g) was slowly added, and the reaction was carried out at 50 °C for 16 hours. After the reaction was complete, MIBK (300 ml) was added, and the mixture was washed six times with 100 ml of pure water. The organic layer was then dried under reduced pressure. MIBK (80 g) was added to the residue to prepare a homogeneous solution, which was then crystallized in MeOH (400 g). The precipitated crystals were separated by filtration, washed twice with MeOH (200 g), and recovered. Compound (A8) was obtained by vacuum drying the recovered crystals at 70 °C.
[0361] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0362] (A8): Mw=2110, Mw / Mn=1.05
[0363] [Synthetic Example 10] Synthesis of Compound (A9)
[0364]
[0365] Compound (B1) 20.0 g, compound (C2) 41.7 g, and 1,2-dichloroethane 300 g were added under a nitrogen atmosphere and a homogeneous dispersion was prepared at an internal temperature of 60 °C. Methanesulfonic acid 22.0 g was slowly added, and the reaction was carried out at an internal temperature of 70 °C for 1 hour. After the reaction was completed, the mixture was cooled to room temperature, and 1000 ml of MIBK (methyl isobutyl ketone) was added. The mixture was washed six times with 200 ml of pure water, and the organic layer was dried under reduced pressure. A homogeneous solution was prepared by adding 200 g of THF to the residue, and crystallization was carried out in 2000 g of IPE (diisopropyl ether). The precipitated crystals were separated by filtration, washed twice with 500 g of IPE, and recovered. Compound (A9) was obtained by vacuum drying the recovered crystals at 70 °C.
[0366] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0367] (A9): Mw=1300, Mw / Mn=1.02
[0368] [Synthetic Example 11] Synthesis of compound (A10)
[0369]
[0370] Compound (A2) 10.0 g, potassium carbonate 6.5 g, and DMF 60 g were added under a nitrogen atmosphere and a homogeneous dispersion was prepared at an internal temperature of 50 °C. Proprynne bromide 2.8 g was slowly added, and the reaction was carried out at an internal temperature of 50 °C for 16 hours. After the reaction was complete, 150 ml of MIBK was added, and the mixture was washed six times with 50 ml of pure water. The organic layer was then dried under reduced pressure. A homogeneous solution was prepared by adding 40 g of MIBK to the residue, and crystallization was carried out in 200 g of MeOH. The precipitated crystals were separated by filtration, washed twice with 100 g of MeOH, and recovered. Compound (A10) was obtained by vacuum drying the recovered crystals at 70 °C.
[0371] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0372] (A10): Mw=1690, Mw / Mn=1.07
[0373] [Synthetic Example 12] Synthesis of Compound (A11)
[0374]
[0375] Under a nitrogen atmosphere, 20.0 g of compound (B3), 25.2 g of compound (C3), and 200 g of 1,2-dichloroethane were added, and a homogeneous dispersion was prepared at an internal temperature of 60°C. 12.9 g of methanesulfonic acid was slowly added, and the reaction was carried out at an internal temperature of 70°C for 3 hours. After the reaction was complete, the mixture was cooled to room temperature, 1000 ml of MIBK was added, and the mixture was washed six times with 200 ml of pure water to solidify the organic layer under reduced pressure. 100 g of THF was added to the residue to prepare a homogeneous solution, and 300 g of hexane was added dropwise while stirring, causing a rice cake-like precipitate to form. After standing for a while, the clear supernatant was decanted. Another 100 g of THF was added to prepare a homogeneous solution, and 300 g of hexane was added to precipitate the rice cake-like precipitate. After standing, the supernatant was decanted. After adding DMF to the precipitate to form a homogeneous solution, the precipitate was removed by vacuum distillation and DMF was added again, and the solution was adjusted to 30 wt% DMF based on the yield.
[0376] 15.4 g of potassium carbonate was added to the obtained DMF solution, and a homogeneous dispersion was prepared under a nitrogen atmosphere and an internal temperature of 50 °C. 13.3 g of propargyl bromide was slowly added, and the reaction was carried out for 16 hours at an internal temperature of 50 °C. After the reaction was complete, 300 ml of MIBK was added, and the mixture was washed six times with 100 ml of pure water. The organic layer was then dried under reduced pressure. 80 g of MIBK was added to the residue to prepare a homogeneous solution, which was then crystallized in 400 g of MeOH. The precipitated crystals were separated by filtration, washed twice with 200 g of MeOH, and recovered. The recovered crystals were dried under vacuum at 70 °C to obtain compound (A11).
[0377] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0378] (A11): Mw=1330, Mw / Mn=1.06
[0379] [Synthetic Example 13] Synthesis of Compound (A12)
[0380]
[0381] Under a nitrogen atmosphere, 20.0 g of compound (B4), 12.0 g of compound (C4), and 160 g of 1,2-dichloroethane were added to prepare a homogeneous solution at an internal temperature of 60°C. 10.5 g of methanesulfonic acid was slowly added, and the reaction was carried out at an internal temperature of 70°C for 3 hours. After the reaction was complete, the mixture was cooled to room temperature, 1000 ml of MIBK was added, and the mixture was washed six times with 200 ml of pure water to solidify the organic layer under reduced pressure. 100 g of THF was added to the residue to prepare a homogeneous solution, and 300 g of hexane was added dropwise while stirring to precipitate a rice cake-like precipitate. After standing for a while, the clear supernatant was decanted. Another 100 g of THF was added to prepare a homogeneous solution, and 300 g of hexane was added to precipitate the rice cake-like precipitate. After standing, the supernatant was decanted. After adding DMF to the precipitate to form a homogeneous solution, the precipitate was removed by vacuum distillation and DMF was added again, and the solution was adjusted to 30 wt% DMF based on the yield.
[0382] Potassium carbonate (22.6 g) was added to the resulting DMF solution, and a homogeneous dispersion was prepared under a nitrogen atmosphere and an internal temperature of 50 °C. Propylbromine (19.5 g) was slowly added, and the reaction was carried out at 50 °C for 16 hours. After the reaction was complete, MIBK (300 ml) was added, and the mixture was washed six times with 100 ml of pure water. The organic layer was then dried under reduced pressure. MIBK (80 g) was added to the residue to prepare a homogeneous solution, which was then crystallized in MeOH (400 g). The precipitated crystals were separated by filtration, washed twice with MeOH (200 g), and recovered. The recovered crystals were dried under vacuum at 70 °C to obtain compound (A12).
[0383] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0384] (A12): Mw=1540, Mw / Mn=1.03
[0385] [Synthetic Example 14] Synthesis of Compound (A13)
[0386]
[0387] Under a nitrogen atmosphere, 20.0 g of compound (B7), 15.1 g of compound (C1), and 200 g of 1,2-dichloroethane were added to prepare a homogeneous solution at an internal temperature of 60°C. 9.1 g of methanesulfonic acid was slowly added, and the reaction was carried out at an internal temperature of 70°C for 3 hours. After the reaction was complete, the mixture was cooled to room temperature, 1000 ml of MIBK was added, and the mixture was washed six times with 200 ml of pure water to solidify the organic layer under reduced pressure. 120 g of THF was added to the residue to prepare a homogeneous solution, and 350 g of hexane was added dropwise while stirring to precipitate a rice cake-like precipitate. After standing for a short time, the clear supernatant was decanted. 120 g of THF was added again to prepare a homogeneous solution, and 350 g of hexane was added to precipitate another rice cake-like precipitate. After standing, the supernatant was decanted. After adding DMF to the precipitate to form a homogeneous solution, the precipitate was removed by vacuum distillation and DMF was added again, and the solution was adjusted to 30 wt% DMF based on the yield.
[0388] 29.3 g of potassium carbonate was added to the obtained DMF solution, and a homogeneous dispersion was prepared under a nitrogen atmosphere and an internal temperature of 50 °C. 25.2 g of propargyl bromide was slowly added, and the reaction was carried out at 50 °C for 16 hours. After the reaction was complete, 400 ml of MIBK was added, and the mixture was washed six times with 100 ml of pure water. The organic layer was then dried under reduced pressure. 100 g of MIBK was added to the residue to prepare a homogeneous solution, which was then crystallized in 500 g of MeOH. The precipitated crystals were separated by filtration, washed twice with 200 g of MeOH, and recovered. The recovered crystals were dried under vacuum at 70 °C to obtain compound (A13).
[0389] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0390] (A13): Mw=1810, Mw / Mn=1.04
[0391] In the synthesis of the comparative examples of compounds (R1) to (R3), the following compounds (a1) to (a3) were used for synthesis.
[0392]
[0393] [Comparative Synthesis Example 1] Comparative Example: Synthesis of Compound (R1)
[0394]
[0395] Under a nitrogen atmosphere, 10.00 g of compound (a1), 4.76 g of potassium carbonate, and 50 g of DMF were prepared into a homogeneous dispersion at an internal temperature of 50°C. 3.72 g of propargyl bromide was slowly added dropwise, and the reaction was carried out at 50°C for 16 hours. After cooling to room temperature, 100 g of methyl isobutyl ketone and 50 g of pure water were added to prepare a homogeneous solution, and the aqueous layer was removed. The organic layer was then washed twice with 30 g of 3.0% nitric acid aqueous solution and five times with 30 g of pure water, and dried under reduced pressure. 30 g of THF was added to the residue, and crystallization was induced with 100 g of methanol. The precipitated crystals were separated by filtration, washed twice with 60 g of methanol, and recovered. The recovered crystals were dried under vacuum at 70°C to obtain (R1).
[0396] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0397] (R1): Mw=960, Mw / Mn=1.07
[0398] [Comparative Synthesis Example 2] Comparative Example: Synthesis of Compound (R2)
[0399]
[0400] Under a nitrogen atmosphere, 78.8 g of compound (a2), 21.6 g of 37% formalin solution, and 250 g of 1,2-dichloroethane were prepared into a homogeneous solution at a liquid temperature of 70°C. Then, 5 g of methanesulfonic acid was slowly added, and the mixture was stirred at a liquid temperature of 80°C for 12 hours. After cooling to room temperature, 500 g of MIBK was added, and the organic layer was washed five times with 200 g of pure water. The organic layer was then dried under reduced pressure. 300 mL of THF was added to the residue, and the polymer was redetermined with 2000 mL of hexane. The precipitated polymer was separated by filtration and dried under reduced pressure to obtain compound (R2).
[0401] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0402] (R2): Mw=2720, Mw / Mn=1.55
[0403] [Comparative Synthesis Example 3] Comparative Example: Synthesis of Compound (R3)
[0404]
[0405] Under a nitrogen atmosphere, 90.1 g of compound (a3), 10.5 g of 37% formalin solution, and 270 g of 2-methoxy-1-propanol were prepared into a homogeneous solution at a liquid temperature of 80°C. Then, 18 g of a 20% p-toluenesulfonic acid solution in 2-methoxy-1-propanol was slowly added, and the mixture was stirred at a liquid temperature of 110°C for 8 hours. After cooling to room temperature, 600 g of MIBK was added, and the organic layer was washed five times with 200 g of pure water. The organic layer was then dried under reduced pressure. 320 g of THF was added to the residue, and the polymer was redeprecipitated with 1350 g of hexane. The precipitated polymer was separated by filtration and dried under reduced pressure to obtain compound (R3).
[0406] When calculating the weight-average molecular weight (Mw) and dispersion (Mw / Mn) using GPC, the following results are obtained.
[0407] (R3): Mw=3700, Mw / Mn=2.82
[0408] The structural formulas, weight-average molecular weights (Mw), and dispersities (Mw / Mn) of the compounds obtained above are shown in Tables 1 and 2-1. In addition, the structural formulas, Mw, and Mw / Mn of compounds (R1) to (R3) used in the comparative examples are also shown in Table 2-2.
[0409] [Table 1]
[0410]
[0411] [Table 2-1]
[0412]
[0413] [Table 2-2]
[0414]
[0415] Preparation of organic film forming materials (UDL-1 to 19, comparative examples UDL-1 to 3)
[0416] Compounds (A1) to (A13) and (R1) to (R3) were dissolved in a solvent containing 0.1% by mass of surfactant FC-4430 (manufactured by Sumitomo 3M) at the proportions shown in Table 3, and filtered through a 0.1 μm fluoropolymer filter to prepare organic membrane forming materials (UDL-1 to 19, Comparative Examples UDL-1 to 3). In the preparation of UDL-1 to 15, propylene glycol monomethyl ether acetate (PGMEA) was used as the solvent. In the preparation of UDL-16 to 19, a mixture of PGMEA and either (S1) 1,6-diacetoxyhexane (boiling point 260°C) or (S2) tripropylene glycol monomethyl ether (boiling point 242°C) was used as the solvent. In the preparation of Comparative Examples UDL-1 to 3, PGMEA was used as the solvent.
[0417] [Table 3]
[0418]
[0419] Example 1 Solvent Resistance Test (Examples 1-1 to 1-19, Comparative Examples 1-1 to 1-3)
[0420] The organic film forming materials (UDL-1 to 19, comparative UDL-1 to 3) prepared above were coated on a silicon substrate and calcined at 400°C for 60 seconds under a nitrogen gas flow with oxygen concentration controlled to below 0.2 vol%. The film thickness was then measured. PGMEA solvent was applied to the film, left to stand for 30 seconds, and then the PGMEA was evaporated by rotary drying at 100°C for 60 seconds. The film thickness was then measured. Calculate the difference in film thickness before and after PGMEA treatment (residual film ratio: (b / a)×100). The results are shown in Table 4 below.
[0421] [Table 4]
[0422]
[0423] As shown in Table 4, the organic film-forming materials of the present invention (Examples 1-1 to 1-19) exhibit a residual film rate of over 99.5% after PGMEA treatment, and crosslinking reaction occurs even under a nitrogen atmosphere, demonstrating sufficient solvent resistance. In contrast, in Comparative Examples 1-3, since there are no substituents that can become crosslinking groups, the residual film rate after PGMEA treatment is less than 50%, no curing reaction occurs, and therefore, no solvent resistance is exhibited. Based on these results, it can be concluded that the substituent represented by OR3, introduced as a substituent, effectively functions as a thermal crosslinking group.
[0424] Example 2: Evaluation of heat resistance properties (Examples 2-1 to 2-19, Comparative Examples 2-1 to 2-3)
[0425] The aforementioned organic film forming materials (UDL-1 to 19, and comparative UDL-1 to 3) were coated onto a silicon substrate and calcined at 180°C in atmospheric conditions to form a 200 nm coated film. The film thickness was then measured. The substrate was further calcined at 400°C for 10 minutes under a nitrogen gas flow with oxygen concentration controlled to below 0.2 vol%, and the film thickness was measured. The residual film ratio is calculated by dividing the film thickness B by the film thickness A. The results are shown in Table 5.
[0426] [Table 5]
[0427]
[0428] As shown in Table 5, the organic film-forming materials of the present invention (Examples 2-1 to 2-19) exhibited a film thickness reduction of less than 3% after calcination at 400°C for 10 minutes. The organic film-forming materials of the present invention also maintained their film thickness after calcination at 400°C, demonstrating high heat resistance. Among these, Examples 2-1 to 2-5, 2-11, and 2-16 to 2-18, which contain compounds with a structure having n2=1 and n3=2, showed even smaller film thickness reductions. In contrast, Comparative Example 2-1, which is a divalent compound, and Comparative Example 2-2, which does not have a fluorene structure, showed a significant film thickness reduction of over 10%. Comparative Example 2-3, which does not have crosslinking groups, also showed a film thickness reduction of over 10%. Based on the above results, it can be concluded that a dense and highly heat-resistant film is formed by compounds having a multivalent backbone and a benzene or naphthalene structure.
[0429] Example 3: Evaluation of Landfill Characteristics (Examples 3-1 to 3-19, Comparative Examples 3-1 to 3-3)
[0430] like Figure 3Therefore, the aforementioned organic film forming materials (UDL-1 to 19, and comparative UDL-1 to 3) were respectively coated onto a SiO2 wafer substrate with a dense hole pattern (hole diameter of 0.16 μm, hole depth of 0.50 μm, and center-to-center distance between two adjacent holes of 0.32 μm). The substrate was then calcined at 400°C for 60 seconds using a nitrogen gas flow under a controlled oxygen concentration of 0.2% by volume to form organic film 8. The substrate used has… Figure 3 The substrate 7 (SiO2 wafer substrate) shows a dense hole pattern as shown in (G) (top view) and (H) (cross-sectional view). The cross-sectional shape of each obtained wafer substrate was observed using a scanning electron microscope (SEM) to confirm whether the holes were filled with an organic film without voids (vacuums). The results are shown in Table 6. When using an organic film forming material with poor filling properties, voids were generated inside the holes in this evaluation. When using an organic film forming material with good filling properties, voids were generated inside the holes in this evaluation. Figure 3 As shown in (I), the pores are filled with organic film without any voids.
[0431] [Table 6]
[0432] Example 3-1 UDL-1 none Example 3-2 UDL-2 none Example 3-3 UDL-3 none Examples 3-4 UDL-4 none Examples 3-5 UDL-5 none Examples 3-6 UDL-6 none Examples 3-7 UDL-7 none Examples 3-8 UDL-8 none Examples 3-9 UDL-9 none Examples 3-10 UDL-10 none Example 3-11 UDL-11 none Example 3-12 UDL-12 none Example 3-13 UDL-13 none Example 3-14 UDL-14 none Example 3-15 UDL-15 none Example 3-16 UDL-16 none Example 3-17 UDL-17 none Example 3-18 UDL-18 none Example 3-19 UDL-19 none Comparative Example 3-1 Comparative Example UDL-1 none Comparative Example 3-2 Comparative Example UDL-2 none Comparative Example 3-3 Comparative example UDL-3 have
[0433] As shown in Table 6, it can be confirmed that the organic film forming material of the present invention (Examples 3-1 to 3-19) can fill the pore pattern without generating voids, exhibiting good filling characteristics. In Comparative Examples 3-1 and 3-2, as the results of the heat resistance evaluation showed, insufficient heat resistance was observed, but no voids were observed. On the other hand, in Comparative Example 3-3, not only was the heat resistance poor, but voids were also generated due to insufficient crosslinking, resulting in poor filling characteristics. Based on these results, it can be confirmed that the organic film forming material of the present invention has good filling characteristics.
[0434] Example 4: Evaluation of Flattening Characteristics (Examples 4-1 to 4-19, Comparative Examples 4-1 to 4-3)
[0435] Organic film forming materials (UDL-1 to 19, and comparative UDL-1 to 3) were respectively coated on patterns with large isolated grooves. Figure 4 On a substrate 9 (SiO2 wafer substrate) with a trench width of 10 μm and a trench depth of 0.10 μm, after calcination at 400°C for 60 seconds under a nitrogen gas flow with an oxygen concentration controlled to below 0.2 vol%, the height difference between the trench portion and the non-trench portion of the organic film 10 was measured. Figure 4The delta (10) in (K) was observed using an NX10 atomic force microscope (AFM) manufactured by Park Systems. The results are shown in Table 7. In this evaluation, the smaller the height difference, the better the planarization characteristics. It should be noted that in this evaluation, an organic film forming material with a film thickness of about 0.2 μm was typically used to planarize a trench pattern with a depth of 0.10 μm, which is a stringent evaluation condition for assessing the quality of planarization characteristics.
[0436] [Table 7]
[0437]
[0438] As shown in Table 7, it can be confirmed that the organic film forming material of the present invention (Examples 4-1 to 4-19) exhibits a smaller height difference between the grooved and non-grooved portions of the organic film compared to Comparative Examples 4-1 to 4-3, resulting in excellent planarization characteristics. In Comparative Examples 4-1 to 4-2, as the results of the heat resistance evaluation were observed, the heat resistance was insufficient. While landfill performance was ensured as in the landfill performance evaluation, the film shrank during high-temperature baking, resulting in deteriorated planarity. Furthermore, in Comparative Example 4-3, poor planarization characteristics resulted from insufficient crosslinking. Moreover, comparing Examples 4-15 to 4-19, which contained a high-boiling-point solvent, with Examples 4-1, 4-2, 4-4, and 4-6, which did not contain a high-boiling-point solvent, it is evident that the planarity was further improved by adding a high-boiling-point solvent. Based on these results, it can be concluded that due to the excellent heat resistance of the organic film forming material of the present invention, film shrinkage during high-temperature baking is suppressed, exhibiting excellent planarization characteristics.
[0439] Example 5: Fit Test (Examples 5-1 to 5-15, Comparative Examples 5-1 to 5-2)
[0440] The aforementioned organic film forming materials (UDL-1 to 15, Comparative UDL-1 to 2) were coated onto a SiO2 wafer substrate. An organic film with a thickness of 200 nm was formed by baking at 400°C for 60 seconds under a nitrogen gas flow with oxygen concentration controlled to below 0.2% by volume. The wafer with the organic film was cut into 1×1 cm squares, and aluminum pins with epoxy adhesive were mounted onto the cut wafers using a special fixture. Subsequently, the wafers were heated in an oven at 150°C for 1 hour to bond the aluminum pins to the substrate. After cooling to room temperature, the initial adhesion was evaluated using a film adhesion strength tester (Sebastian Five-A) and by measuring resistance. It should be noted that the adhesion test could not be performed on Comparative Example UDL-3, for which solvent resistance could not be guaranteed in Example 1.
[0441] Figure 5 The diagram below illustrates the method for measuring the tightness of the seal. Figure 5In the diagram, 11 represents the silicon wafer (substrate), 12 represents the cured coating, 13 represents the aluminum pin with adhesive, 14 represents the support platform, 15 represents the clamp, and 16 represents the stretching direction. The adhesion force is the average value measured at these 12 points; a higher value indicates better adhesion of the adhesive film to the substrate. Adhesion is evaluated by comparing the obtained values. The results are shown in Table 8.
[0442] [Table 8]
[0443]
[0444] As shown in Tables 8, Examples 5-1 to 5-15, the organic film materials obtained using the compounds of the present invention exhibit higher adhesion compared to Comparative Examples 5-1 and 5-2. Examples 5-1 to 5-6, 5-8, and 5-10 to 5-15, which contain a structure with n3 = 2, exhibit high adhesion, while Examples 5-8, 5-12, and 5-13, which contain a structure with R3 = H, exhibit particularly high adhesion. On the other hand, Comparative Examples 5-1 and 5-2 exhibit low adhesion due to insufficient heat resistance. Based on these results, it can also be seen that the compounds of the present invention exhibit high heat resistance and good adhesion to the substrate.
[0445] Example 6 Pattern Formation Experiment 1 (Examples 6-1 to 6-19, Comparative Example 6-1)
[0446] The aforementioned organic film forming materials (UDL-1 to 19, Comparative UDL-1) were coated onto a silicon wafer substrate with a 300 nm SiO2 film. The substrate was then calcined at 400°C for 60 seconds under a nitrogen gas flow with oxygen concentration controlled to below 0.2 vol%, forming an organic film (lower resist layer). A CVD-SiON hard mask was formed on this film. An organic antireflective film material (ARC-29A: manufactured by Nissan Chemical Co., Ltd.) was then coated onto this film and baked at 210°C for 60 seconds, forming an 80 nm thick organic antireflective film. An ArF monolayer resist (upper resist layer) was then coated onto this film and baked at 105°C for 60 seconds, forming a 100 nm thick photoresist film (upper resist layer). An immersion protective film material (TC-1) was then coated onto the photoresist film and baked at 90°C for 60 seconds, forming a 50 nm thick protective film. It should be noted that comparative examples UDL-2 and UDL-3 could not form CVD-SiON hard masks due to poor heat resistance and crosslinking properties, and therefore could not proceed to subsequent patterning experiments.
[0447] As a top-layer resist material (a single-layer resist for ArF), the polymer (RP1), acid-generating agent (PAG1), and basic compound (Amine1) are dissolved in a solvent containing 0.1% by mass of FC-430 (manufactured by Sumitomo 3M) in the proportions shown in Table 9, and then filtered using a 0.1 μm fluoropolymer filter.
[0448] [Table 9]
[0449]
[0450] The following shows the polymer (RP1), acid-producing agent (PAG1), and basic compound (Amine1) used.
[0451]
[0452] As a liquid-immersion protective membrane material (TC-1), the protective membrane polymer (PP1) was dissolved in an organic solvent at the proportions shown in Table 10, and then filtered using a 0.1 μm fluoropolymer filter.
[0453] [Table 10]
[0454]
[0455] The following shows the polymer used (PP1).
[0456]
[0457] Next, exposure was performed using an ArF immersion exposure apparatus (Nikon; NSR-S610C, NA1.30, σ0.98 / 0.65, 35-degree dipole s-polarized illumination, 6% halftone phase-shift mask), followed by baking at 100°C for 60 seconds (PEB), and development with a 2.38% by mass tetramethylammonium hydroxide (TMAH) aqueous solution for 30 seconds, resulting in 55nm 1:1 positive lines and spatial patterns.
[0458] Next, using the Telius etching apparatus manufactured by Tokyo Gosei Corporation, dry etching was performed on the organic antireflective film and the CVD-SiON hard mask using the resist pattern as a mask to form a hard mask pattern. Using the resulting hard mask pattern as a mask, the organic film was etched to form an organic film pattern. Finally, using the resulting organic film pattern as a mask, the SiO2 film was etched. The etching conditions are shown below.
[0459] Conditions for transferring resist patterns to a SiON hard mask.
[0460]
[0461] Conditions for transferring hard mask patterns onto organic films.
[0462]
[0463] Conditions for transferring organic film patterns onto SiO2 films.
[0464]
[0465] The cross-section of the pattern was observed using an electron microscope (Zhong 4700) manufactured by Hitachi, Ltd., and the results are shown in Table 11.
[0466] [Table 11]
[0467]
[0468] As shown in Table 11, the results of the organic film forming materials according to the present invention (Examples 6-1 to 6-19) confirm that, in all cases, the resist upper film pattern is ultimately well transferred to the substrate, and the organic film forming materials of the present invention are applicable to microfabrication based on the multilayer resist method. In Comparative Example 6-1, although the heat resistance was insufficient, patterning was still possible.
[0469] Furthermore, the organic film forming materials (UDL1-19) of the present invention can form organic films that exhibit excellent adhesion to the substrate, thereby suppressing the peeling of the CVD-SiON hard mask formed directly above the organic film and the resist upper layer film formed thereon. As a result, in Examples 6-1 to 6-19, as described above, the resist upper layer film pattern can ultimately be well transferred to the substrate.
[0470] Example 7 Pattern Formation Experiment 2 (Examples 7-1 to 7-19, Comparative Example 7-1)
[0471] The above-mentioned organic film forming materials (UDL-1 to 19, Comparative UDL-1) were coated on SiO2 wafer substrates with trench patterns (trench width 10 μm, trench depth 0.10 μm). The substrates were calcined at 400°C for 60 seconds under a nitrogen gas flow with oxygen concentration controlled to below 0.2 vol%. Otherwise, the coated films were formed using the same method as in Pattern Forming Experiment 1, and the patterns were patterned and dry etched. The shapes of the formed patterns were observed, and the results are shown in Table 12.
[0472] [Table 12]
[0473]
[0474] As shown in Table 12, the results of the organic film forming materials according to the present invention (Examples 7-1 to 7-19) confirm that, in any case, the resist upper film pattern is ultimately well transferred to the substrate, and the organic film forming materials of the present invention are applicable to microfabrication based on the multilayer resist method. On the other hand, in Comparative Example 7-1, as the results of the planarization characteristic evaluation show, the poor planarization characteristics caused pattern collapse during pattern processing, and ultimately a good pattern could not be obtained.
[0475] Furthermore, the organic film forming material of the present invention (Examples 7-1 to 7-19) can form an organic film that exhibits excellent adhesion to the substrate, thereby suppressing the peeling of the CVD-SiON hard mask formed directly above the organic film and the resist upper layer film formed thereon. As a result, in Examples 7-1 to 7-19, as described above, the resist upper layer film pattern can ultimately be well transferred to the substrate.
[0476] In summary, it is clear that if the organic film forming material of the present invention contains the organic film forming compound of the present invention, it possesses heat resistance of over 400°C, excellent adhesion to the substrate, and high packing / planarization characteristics even in an oxygen-free inactive gas environment. Therefore, it is extremely useful as an organic film forming material used in multilayer resist methods. Furthermore, if the pattern forming method of the present invention uses it, fine patterns can be formed with high precision even when the processed body is a substrate with height differences.
[0477] It should be noted that the present invention is not limited to the above embodiments. The above embodiments are illustrative examples, and any technical solution having a substantially the same structure and achieving the same effect as the technical concept described in the claims of the present invention is included within the protection scope of the present invention.
[0478] This instruction manual includes the following methods.
[0479] [1]: An organic film forming material, characterized in that it contains (A) an organic film forming compound represented by the following general formula (1A) and (B) an organic solvent.
[0480]
[0481] (In the formula, Y is an organic group with an n1 valence, a nitrogen atom with a trivalent valence, or a carbon atom with a tetravalent valence; n1 is an integer from 3 to 8; X is a partial structure shown in the following general formula (1B).)
[0482]
[0483] (In the formula, dashed lines represent connecting bonds. R1 and R2 represent halogen atoms, alkyl groups with 1 to 4 carbon atoms, alkoxy groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, or alkenyl groups with 2 to 4 carbon atoms. The hydrogen atoms on the carbon atoms constituting the aforementioned alkyl, alkoxy, alkynyl, or alkenyl groups may optionally be replaced by fluorine atoms. In addition, the aromatic rings that can be replaced by R1 may optionally form a bridging structure by means of a single bond or by means of a divalent group obtained by removing one hydrogen atom from the aforementioned R1. n4 and n5 represent integers from 0 to 2. Ar1 and Ar2 represent benzene rings or naphthalene rings, respectively. n2 represents 0 or 1, n3 represents 1 or 2, and R3 represents a hydrogen atom or an alkyl group with 1 to 4 carbon atoms, an alkynyl group with 2 to 4 carbon atoms, or an alkenyl group with 2 to 4 carbon atoms.)
[0484] [2]: The organic film forming material according to [1] is characterized in that R3 in the aforementioned general formula (1B) is any one of the groups shown in the following formula (1C).
[0485]
[0486] (The dashed lines in the above formula represent connectors.)
[0487] [3]: The organic film forming material according to [1] or [2] is characterized in that n1 in the aforementioned general formula (1A) is 3 or 4.
[0488] [4]: The organic film forming material according to any one of [1] to [3] is characterized in that n2 in the aforementioned general formula (1B) is 1.
[0489] [5]: The organic film forming material according to any one of [1] to [4] is characterized in that Y in the aforementioned general formula (1A) is any of the partial structures shown in the following formula (1D).
[0490]
[0491] (The dashed lines in the above formula represent connecting bonds, and R4 represents a hydrogen atom or a methyl group.)
[0492] [6]: The organic film forming material according to any one of [1] to [5] is characterized in that the ratio of the weight average molecular weight Mw to the number average molecular weight Mn of the aforementioned component (A) based on gel permeation chromatography is 1.00≤Mw / Mn≤1.10.
[0493] [7]: The organic film forming material according to any one of [1] to [6] is characterized in that the aforementioned (B) organic solvent is a mixture of one or more organic solvents with a boiling point below 180°C and one or more organic solvents with a boiling point above 180°C.
[0494] [8]: The organic film forming material according to any one of [1] to [7] is characterized in that the aforementioned organic film forming material further contains one or more of (C) an acid-producing agent, (D) a surfactant, (E) a crosslinking agent and (F) a plasticizer.
[0495] [9]: A substrate for manufacturing a semiconductor device, characterized in that an organic film is formed on the substrate by curing an organic film forming material as described in any one of [1] to [8].
[0496]
[10] : A method for forming an organic film, characterized in that it is a method for forming an organic film used in the manufacturing process of a semiconductor device, wherein an organic film forming material as described in any one of [1] to [8] is spin-coated onto a substrate to be processed, and the substrate to be processed coated with the organic film forming material is subjected to heat treatment in an inactive gas atmosphere at a temperature of 50°C or higher and 600°C or lower for a range of 5 seconds to 7200 seconds to obtain a cured film.
[0497]
[11] : A method for forming an organic film, characterized in that it is a method for forming an organic film used in the manufacturing process of a semiconductor device, wherein an organic film forming material as described in any one of [1] to [8] is spin-coated onto a substrate to be processed, and the substrate to be processed coated with the organic film forming material is heat-treated in air at a temperature of 50°C or higher and 300°C or lower for a range of 5 to 600 seconds to form a coated film, and then heat-treated in an inactive gas atmosphere at a temperature of 200°C or higher and 600°C or lower for a range of 10 to 7200 seconds to obtain a cured film.
[0498]
[12] : The method for forming an organic membrane according to
[10] or
[11] is characterized in that the oxygen concentration in the aforementioned inactive gas is set to less than 1% by volume.
[0499]
[13] : The method for forming an organic film according to any one of
[10] to
[12] is characterized in that, as the aforementioned substrate to be processed, a substrate having a structure with a height of 30 nm or more or a height difference is used.
[0500]
[14] : A pattern forming method, characterized in that an organic film is formed on a workpiece using an organic film forming material as described in any one of [1] to [8], a silicon-containing photoresist intermediate film is formed on the organic film using a silicon-containing photoresist intermediate film material, a photoresist upper film is formed on the silicon-containing photoresist intermediate film using a photoresist composition, a circuit pattern is formed on the photoresist upper film, a pattern is transferred to the aforementioned silicon-containing photoresist intermediate film by etching using the photoresist upper film with the pattern formed thereon as a mask, a pattern is transferred to the aforementioned organic film by etching using the photoresist intermediate film with the pattern transferred thereon as a mask, and then a pattern is transferred to the aforementioned workpiece by etching using the organic film with the pattern transferred thereon as a mask.
[0501]
[15] : A pattern forming method, characterized in that an organic film is formed on a workpiece using an organic film forming material as described in any one of [1] to [8], a silicon-containing photoresist intermediate film is formed on the organic film using a silicon-containing photoresist intermediate film material, an organic anti-reflective film is formed on the silicon-containing photoresist intermediate film, a photoresist upper film is formed on the organic anti-reflective film using a photoresist composition to form a photoresist upper film to form a four-layer film structure, a circuit pattern is formed on the photoresist upper film, the photoresist upper film with the pattern is used as a mask, the pattern is transferred to the aforementioned organic anti-reflective film and the aforementioned silicon-containing photoresist intermediate film by etching, the pattern is transferred to the aforementioned organic film by etching using the silicon-containing photoresist intermediate film with the transferred pattern as a mask, and then, the pattern is transferred to the aforementioned workpiece by etching using the organic film with the transferred pattern as a mask.
[0502]
[16] : A pattern forming method, characterized in that an organic film is formed on a workpiece using an organic film forming material as described in any one of [1] to [8], an inorganic hard mask selected from silicon oxide film, silicon nitride film, silicon nitride film, titanium oxide film, and titanium nitride film is formed on the organic film, a photoresist upper layer film is formed on the inorganic hard mask using a photoresist composition, a circuit pattern is formed on the photoresist upper layer film, the photoresist upper layer film with the pattern is used as a mask, the pattern is transferred to the aforementioned inorganic hard mask by etching, the pattern is transferred to the aforementioned organic film by etching using the inorganic hard mask with the transferred pattern as a mask, and then the pattern is transferred to the aforementioned workpiece by etching using the organic film with the transferred pattern as a mask.
[0503]
[17] : A pattern forming method, characterized in that an organic film is formed on a workpiece using an organic film forming material as described in any one of [1] to [8], an inorganic hard mask selected from silicon oxide film, silicon nitride film, silicon nitride film, titanium oxide film, and titanium nitride film is formed on the organic film, an organic antireflective film is formed on the inorganic hard mask, a photoresist composition is used to form a photoresist top layer film on the organic antireflective film to form a four-layer film structure, a circuit pattern is formed on the photoresist top layer film, the photoresist top layer film with the pattern is used as a mask, the pattern is transferred to the aforementioned organic antireflective film and the aforementioned inorganic hard mask by etching, the pattern is transferred to the aforementioned organic film by etching using the inorganic hard mask with the transferred pattern as a mask, and then the pattern is transferred to the aforementioned workpiece by etching using the organic film with the transferred pattern as a mask.
[0504]
[18] : The pattern forming method according to
[16] or
[17] is characterized in that the aforementioned inorganic hard mask is formed by CVD or ALD.
[0505]
[19] : The pattern forming method according to any one of
[14] to
[18] is characterized in that, in the formation of the aforementioned circuit pattern, the circuit pattern is formed by photolithography, direct electron beam drawing, nanoimprinting or a combination thereof using light with a wavelength of 10 nm or more and 300 nm or less.
[0506]
[20] : The pattern forming method according to any one of
[14] to
[19] is characterized in that, in the formation of the aforementioned circuit pattern, the circuit pattern is developed by alkaline development or organic solvent.
[0507]
[21] : The pattern forming method according to any one of
[14] to
[20] is characterized in that the aforementioned workpiece is a workpiece using a semiconductor device substrate or having a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film and a metal nitride film formed on the semiconductor device substrate.
[0508]
[22] : The pattern forming method according to
[21] is characterized in that, as the aforementioned workpiece, a workpiece comprising silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum or alloys thereof is used.
[0509]
[23] : A compound represented by the following general formula (1A).
[0510]
[0511] (In the formula, Y is an organic group with an n1 valence, a nitrogen atom with a trivalent valence, or a carbon atom with a tetravalent valence, n1 is an integer from 3 to 8, and X is a partial structure shown in the following general formula (1B).)
[0512]
[0513] (In the formula, dashed lines represent connecting bonds. R1 and R2 represent halogen atoms, alkyl groups with 1 to 4 carbon atoms, alkoxy groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, or alkenyl groups with 2 to 4 carbon atoms. The hydrogen atoms on the carbon atoms constituting the aforementioned alkyl, alkoxy, alkynyl, or alkenyl groups may optionally be replaced by fluorine atoms. In addition, the aromatic rings that can be replaced by R1 may optionally form a bridging structure by means of a single bond or by means of a divalent group obtained by removing one hydrogen atom from the aforementioned R1. n4 and n5 represent integers from 0 to 2. Ar1 and Ar2 represent benzene rings or naphthalene rings, respectively. n2 represents 0 or 1, n3 represents 1 or 2; R3 represents a hydrogen atom or an alkyl group with 1 to 4 carbon atoms, an alkynyl group with 2 to 4 carbon atoms, or an alkenyl group with 2 to 4 carbon atoms.)
[0514]
[24] : The compound according to
[23] is characterized in that R3 in the aforementioned general formula (1B) is any of the groups shown in the following formula (1C).
[0515]
[0516] (The dashed lines in the above formula represent connectors.)
[0517]
[25] : The compound according to
[23] or
[24] is characterized in that n1 in the aforementioned general formula (1A) is 3 or 4.
[0518]
[26] : The compound according to any one of
[23] to
[25] is characterized in that n2 in the aforementioned general formula (1B) is 1.
[0519]
[27] : The compound according to any one of
[23] to
[26] is characterized in that Y in the aforementioned general formula (1A) is any of the partial structures shown in the following formula (1D).
[0520]
[0521] (The dashed lines in the above formula represent connecting bonds, and R4 represents a hydrogen atom or a methyl group.)
Claims
1. A material for forming organic films, characterized in that, It contains (A) an organic film-forming compound represented by the following general formula (1A) and (B) an organic solvent. In formula (1A), Y is an organic group with an n1 valence, a nitrogen atom with a trivalent valence, or a carbon atom with a tetravalent valence; n1 is an integer from 3 to 8; X is a partial structure shown in the following general formula (1B). In formula (1B), dashed lines represent connecting bonds; R1 and R2 represent halogen atoms, alkyl groups with 1 to 4 carbon atoms, alkoxy groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, or alkenyl groups with 2 to 4 carbon atoms, wherein the hydrogen atoms on the carbon atoms constituting the alkyl, alkoxy, alkynyl, or alkenyl groups are optionally replaced by fluorine atoms; furthermore, the aromatic rings that can be replaced by R1 can optionally form a bridging structure by means of single bonds or by means of divalent groups obtained by removing one hydrogen atom from R1; n4 and n5 represent integers from 0 to 2; Ar1 and Ar2 represent benzene rings or naphthalene rings, respectively; n2 represents 0 or 1; n3 represents 1 or 2; R3 is any of the groups shown in formula (1C) below. The dashed lines in the above formula represent connecting keys.
2. The material for forming organic films according to claim 1, characterized in that, In the general formula (1A), n1 is 3 or 4.
3. The material for forming organic films according to claim 1, characterized in that, In the general formula (1B), n2 is 1.
4. The material for forming organic films according to claim 1, characterized in that, In the general formula (1A), Y is any of the partial structures shown in the following formula (1D). In the above formula, the dashed line represents a connecting bond; R4 represents a hydrogen atom or a methyl group.
5. The material for forming organic films according to claim 1, characterized in that, The ratio of the weight-average molecular weight Mw to the number-average molecular weight Mn of component (A) based on gel permeation chromatography is 1.00 ≤ Mw / Mn ≤ 1.
10.
6. The material for forming organic films according to claim 1, characterized in that, The organic solvent (B) is a mixture of one or more organic solvents with a boiling point below 180°C and one or more organic solvents with a boiling point above 180°C.
7. The material for forming organic films according to claim 1, characterized in that, The organic film forming material further contains one or more of (C) an acid-producing agent, (D) a surfactant, (E) a crosslinking agent, and (F) a plasticizer.
8. A substrate for manufacturing a semiconductor device, characterized in that, An organic film is formed on a substrate by curing the organic film forming material according to any one of claims 1 to 7.
9. A method for forming an organic membrane, characterized in that, It is a method for forming an organic film used in the manufacturing process of a semiconductor device, wherein the organic film forming material according to any one of claims 1 to 7 is spin-coated onto a substrate to be processed, and the substrate to be processed coated with the organic film forming material is subjected to heat treatment in an inactive gas atmosphere at a temperature of 50°C or higher and 600°C or lower for a period of 5 to 7200 seconds to obtain a cured film.
10. A method for forming an organic membrane, characterized in that, This is a method for forming an organic film used in the manufacturing process of a semiconductor device. The method involves spin-coating an organic film forming material according to any one of claims 1 to 7 onto a substrate to be processed. The substrate coated with the organic film forming material is then heat-treated in air at a temperature between 50°C and 300°C for 5 to 600 seconds to form a coated film. Next, a heat treatment is applied in an inert gas atmosphere at a temperature between 200°C and 600°C for 10 to 7200 seconds to obtain a cured film.
11. The method for forming an organic membrane according to claim 9, characterized in that, The oxygen concentration in the inactive gas is set to be below 1% by volume.
12. The method for forming an organic membrane according to claim 9, characterized in that, As the substrate to be processed, a structure with a height of 30 nm or more or a height difference is used.
13. A method for forming a pattern, characterized in that, An organic film is formed on a workpiece using the organic film forming material according to any one of claims 1 to 7. A silicon-containing photoresist intermediate film is formed on the organic film using a silicon-containing photoresist intermediate film material. A photoresist upper film is formed on the silicon-containing photoresist intermediate film using a photoresist composition. A circuit pattern is formed on the photoresist upper film. Using the photoresist upper film with the pattern formed thereon as a mask, the pattern is transferred to the silicon-containing photoresist intermediate film by etching. Using the silicon-containing photoresist intermediate film with the transferred pattern as a mask, the pattern is transferred to the organic film by etching. Furthermore, using the organic film with the transferred pattern as a mask, the pattern is transferred to the workpiece by etching.
14. A method for forming a pattern, characterized in that, An organic film is formed on a workpiece using the organic film forming material according to any one of claims 1 to 7. A silicon-containing photoresist intermediate film is formed on the organic film using a silicon-containing photoresist intermediate film material. An organic antireflective film is formed on the silicon-containing photoresist intermediate film. A photoresist top film is formed on the organic antireflective film using a photoresist composition to form a photoresist top film, thereby forming a four-layer film structure. A circuit pattern is formed on the photoresist top film. Using the photoresist top film with the pattern formed thereon as a mask, a pattern is transferred to the organic antireflective film and the silicon-containing photoresist intermediate film by etching. Using the silicon-containing photoresist intermediate film with the transferred pattern as a mask, a pattern is transferred to the organic film by etching. Furthermore, using the organic film with the transferred pattern as a mask, a pattern is transferred to the workpiece by etching.
15. A method for forming a pattern, characterized in that, An organic film is formed on a workpiece using the organic film forming material according to any one of claims 1 to 7. An inorganic hard mask selected from silicon oxide film, silicon nitride film, silicon nitride film, titanium oxide film, and titanium nitride film is formed on the organic film. A photoresist top layer film is formed on the inorganic hard mask using a photoresist composition. A circuit pattern is formed on the photoresist top layer film. The photoresist top layer film with the pattern is used as a mask. The pattern is transferred to the inorganic hard mask by etching. The pattern is transferred to the organic film by etching. Furthermore, the pattern is transferred to the workpiece by etching using the organic film with the transferred pattern as a mask.
16. A method for forming a pattern, characterized in that, An organic film is formed on a workpiece using the organic film forming material according to any one of claims 1 to 7. An inorganic hard mask selected from silicon oxide film, silicon nitride film, silicon nitride film, titanium oxide film, and titanium nitride film is formed on the organic film. An organic antireflective film is formed on the inorganic hard mask. A photoresist composition is used to form a photoresist top layer film on the organic antireflective film to form a four-layer film structure. A circuit pattern is formed on the photoresist top layer film. Using the photoresist top layer film with the pattern formed as a mask, a pattern is transferred to the organic antireflective film and the inorganic hard mask by etching. Using the inorganic hard mask with the transferred pattern as a mask, a pattern is transferred to the organic film by etching. Furthermore, using the organic film with the transferred pattern as a mask, a pattern is transferred to the workpiece by etching.
17. The pattern forming method according to claim 15, characterized in that, The inorganic hard mask is formed by CVD or ALD.
18. The pattern forming method according to claim 13, characterized in that, In the formation of the circuit pattern, the circuit pattern is formed by photolithography using light with a wavelength of 10 nm or more and 300 nm or less, direct electron beam drawing, nanoimprinting, or a combination thereof.
19. The pattern forming method according to claim 13, characterized in that, In the formation of the circuit pattern, the circuit pattern is developed by alkaline development or organic solvent.
20. The pattern forming method according to claim 13, characterized in that, The workpiece is a workpiece that uses a semiconductor device substrate or has a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal nitride film formed on the semiconductor device substrate.
21. The pattern forming method according to claim 20, characterized in that, As the workpiece, a workpiece comprising silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or alloys thereof is used.
22. A compound represented by the following general formula (1A), In formula (1A), Y is an organic group with an n1 valence, a nitrogen atom with a trivalent valence, or a carbon atom with a tetravalent valence; n1 is an integer from 3 to 8; X is a partial structure shown in the following general formula (1B). In formula (1B), dashed lines represent connecting bonds; R1 and R2 represent halogen atoms, alkyl groups with 1 to 4 carbon atoms, alkoxy groups with 1 to 4 carbon atoms, alkynyl groups with 2 to 4 carbon atoms, or alkenyl groups with 2 to 4 carbon atoms, wherein the hydrogen atoms on the carbon atoms constituting the alkyl, alkoxy, alkynyl, or alkenyl groups are optionally replaced by fluorine atoms; furthermore, the aromatic rings that can be replaced by R1 can optionally form a bridging structure by means of single bonds or by means of divalent groups obtained by removing one hydrogen atom from R1; n4 and n5 represent integers from 0 to 2; Ar1 and Ar2 represent benzene rings or naphthalene rings, respectively; n2 represents 0 or 1; n3 represents 1 or 2; R3 is any of the groups shown in formula (1C) below. The dashed lines in the above formula represent connecting keys.
23. The compound according to claim 22, characterized in that, In the general formula (1A), n1 is 3 or 4.
24. The compound according to claim 22, characterized in that, In the general formula (1B), n2 is 1.
25. The compound according to claim 22, characterized in that, In the general formula (1A), Y is any of the partial structures shown in the following formula (1D). In the above formula, the dashed line represents a connecting bond; R4 represents a hydrogen atom or a methyl group.
Citation Information
Patent Citations
Method and device for forming silicon nitride film, and method for preprocessing of cleaning thereof
JP2002334869A
Material for forming photoresist lower layer film and method for forming pattern
JP2005128509A
Resist lower layer film material and pattern forming method
JP2006285095A
Photoresist undercoat-forming material and patterning process
JP2006293298A
Photoresist underlayer film forming material and pattern forming method
JP2007199653A